Electrode composition for all-solid-state secondary battery, electrode sheet for all-solid-state secondary battery, all-solid-state secondary battery, and method for producing electrode sheet for all-solid-state secondary battery, and method for producing all-solid-state secondary battery
By using amorphous solid electrolytes and active materials in all-solid-state secondary batteries and controlling their particle size ratio and proportion, the problems of dispersion and flexibility of the active material layer are solved, thereby improving the battery's productivity and lifespan.
Patent Information
- Application Number
- CN202380043213.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-01
- Filing Date
- 2023-05-31
- Publication Date
- 2025-01-07
AI Technical Summary
In existing all-solid-state secondary batteries, the reduced amount of dispersion medium during the preparation of the active material layer leads to the aggregation of solid electrolyte and active material, making it difficult to disperse evenly. Furthermore, the active material layer has poor flexibility, affecting battery performance and operability.
An all-solid-state electrode composition for secondary batteries, comprising an amorphous solid electrolyte and active material, is employed. The ratio of the median diameter of the active material to the solid electrolyte is controlled within the range of 0.05 ≤ M/N < 1.2. The ratio of the solid electrolyte to the active material and the water content are optimized to form a high-concentration slurry with excellent dispersion stability.
It achieves excellent dispersion stability and flexibility of the active material layer, shortens the drying process, improves the productivity of all-solid-state secondary batteries, reduces energy loss, and extends battery life.
Smart Images

Figure CN119278515A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrode composition for an all-solid-state secondary battery, an electrode sheet for an all-solid-state secondary battery, an all-solid-state secondary battery, and a method for manufacturing the electrode sheet for an all-solid-state secondary battery and the all-solid-state secondary battery. Background Art
[0002] In the past, organic solvents with high ion conductivity have been used as electrolytes in lithium-ion secondary batteries. However, since organic solvents are flammable, there are safety issues. In addition, since they are in a liquid state, it is difficult to make them compact, and when the battery becomes larger, the capacity limitation also becomes a problem.
[0003] In contrast, all-solid-state secondary batteries such as all-solid-state lithium-ion secondary batteries are one of the next-generation batteries that can solve these problems. The basic structure of an all-solid-state lithium-ion secondary battery, which is one form of an all-solid-state secondary battery, is shown in FIG. Figure 1 In the embodiment of the present invention, the all-solid-state lithium-ion secondary battery 10 has a negative electrode current collector layer 1, a negative electrode active material layer 2, a solid electrolyte layer 3, a positive electrode active material layer 4 and a positive electrode current collector layer 5 in order from the negative electrode side. Each layer is in contact with each other and has an adjacent structure. By adopting this structure, during charging, electrons (e - ) is supplied to the negative electrode side, so that the lithium ions (Li + ) accumulates here. On the other hand, during discharge, the lithium ions (Li + ) returns to the positive electrode side through the solid electrolyte layer 3, so that the electrons are supplied to the working part 6. In the example shown in the figure, a light bulb is used as a model at the working part 6, and it is lit by discharge.
[0004] As described above, in order to obtain desired charge and discharge characteristics in an all-solid-state lithium ion secondary battery, the solid electrolyte layer needs to have excellent lithium ion conductivity.
[0005] As the solid electrolyte constituting the solid electrolyte layer, a sulfide-based solid electrolyte or an oxide-based solid electrolyte is mainly used.
[0006] Since sulfide-based solid electrolytes are soft and plastically deformable, the particles can be bonded together simply by press molding. Therefore, the interface resistance between the particles of sulfide-based solid electrolytes is low and the ion conductivity is excellent. However, sulfide-based solid electrolytes have the problem of reacting with water to produce toxic hydrogen sulfide.
[0007] In contrast, oxide-based solid electrolytes have the advantage of high safety. However, oxide-based solid electrolytes are hard and not prone to plastic deformation. In order to improve the adhesion between particles of oxide-based solid electrolytes, high-temperature sintering treatment is required, which is limited from the perspectives of battery production efficiency and energy costs. For example, Patent Document 1 discloses a solid electrolyte formed of a lithium-containing oxide composed of specific elements, and it is recorded that the solid electrolyte shows high ion conductivity, but in order to use the lithium-containing oxide as a solid electrolyte sheet, a high-temperature sintering treatment is required.
[0008] As a technology to deal with this problem, for example, Patent Document 2 describes a composite comprising a lithium compound and lithium tetraborate, wherein the lithium compound has a lithium ion conductivity of 1.0×10 -6 S / cm or more, and the reduced two-body distribution function G(r) of the lithium tetraborate obtained from the total X-ray scattering measurement shows a specific distribution. According to the technology described in Patent Document 2, although the composite is composed of a lithium-containing oxide, lithium tetraborate undergoes plastic deformation between lithium compounds to play a role in connecting lithium compounds. Therefore, even if the composite is not subjected to a high-temperature sintering treatment, it can be formed into a lithium ion conductor showing good lithium ion conductivity by a pressurization treatment.
[0009] In an all-solid-state secondary battery, the positive electrode active material layer and the negative electrode active material layer (these are also collectively referred to as "active material layers") generally contain a solid electrolyte and an active material in a powdered state. The active material layer is generally prepared by preparing a particle dispersion (slurry) containing a solid electrolyte, an active material, and a dispersion medium (e.g., water), applying the slurry, and drying. Patent document 3 discloses a slurry for an electrode, which is prepared from at least electrolyte particles, active material particles, and a dispersion medium, and the ratio (Db / Da) of the median diameter (Db) of the active material particles to the median diameter (Da) of the electrolyte particles is in the range of 0.1 to 1.0. By using this slurry for an electrode, an electrode having both high electronic conductivity and high ion conductivity can be provided. The electrolyte particles (solid electrolyte) contained in the electrode slurry described in patent document 3 do not contain water in the solid electrolyte.
[0010] Previous technical literature
[0011] Patent Literature
[0012] Patent Document 1: Japanese Patent Application Publication No. 2018-052755
[0013] Patent Document 2: International Publication No. 2021 / 193204
[0014] Patent Document 3: Japanese Patent Application Publication No. 2015-022960 Summary of the invention
[0015] Technical issues to be solved by the invention
[0016] When preparing the active material layer, if the amount of the dispersion medium in the above-mentioned slurry can be reduced, it is possible to efficiently dry, which is preferred from the viewpoint of being able to shorten the manufacturing time. On the other hand, if the amount of the dispersion medium in the slurry is reduced (the solid component in the slurry is highly concentrated), there is a problem that solid electrolytes, solid particles such as active materials are easily agglomerated and it is difficult to achieve uniform dispersion. In addition, if a slurry with poor dispersibility is used, when used as an active material layer, there are the following problems: sufficient flexibility cannot be obtained, cracks and peeling of the active material layer are easily generated, so that the operability deteriorates (the yield rate decreases), and sufficient performance cannot be obtained when assembled into a battery.
[0017] The subject of the present invention is to provide an all-solid-state secondary battery electrode composition that can prepare a high-concentration slurry with excellent dispersion stability of solid particles and the flexibility of the formed active material layer is also excellent. In addition, the subject of the present invention is to provide an all-solid-state secondary battery electrode sheet and an all-solid-state secondary battery using the above-mentioned all-solid-state secondary battery electrode composition. In addition, the subject of the present invention is to provide a method for manufacturing the above-mentioned all-solid-state secondary battery electrode sheet and an all-solid-state secondary battery.
[0018] Means for solving technical problems
[0019] The problems of the present invention are solved by the following means.
[0020] [1]
[0021] An electrode composition for an all-solid-state secondary battery comprises an amorphous solid electrolyte and an active material, wherein:
[0022] The solid electrolyte comprises: a metal oxide containing at least one of an alkali metal element and an alkaline earth metal element and an oxygen element, at least one metal salt of an alkali metal salt and an alkaline earth metal salt, and water.
[0023] The ratio of the median diameter M of the active material to the median diameter N of the solid electrolyte is 0.05≤M / N<1.2.
[0024] [2]
[0025] The electrode composition for an all-solid-state secondary battery according to [1], wherein
[0026] The metal-containing oxide is a lithium-containing oxide containing Li, B, and O, and the metal salt is a lithium salt.
[0027] 〔3〕
[0028] The electrode composition for an all-solid-state secondary battery according to [1] or [2], wherein
[0029] The median diameter N of the solid electrolyte is 5 to 50 μm.
[0030] [4]
[0031] The electrode composition for an all-solid-state secondary battery according to any one of [1] to [3], wherein
[0032] In the above-mentioned electrode composition for all-solid-state secondary batteries, the ratio of the content of the above-mentioned solid electrolyte to the content of the above-mentioned active material is the above-mentioned solid electrolyte: the above-mentioned active material = 20:80 to 80:20 in terms of mass ratio.
[0033] 〔5〕
[0034] The electrode composition for an all-solid-state secondary battery according to any one of [1] to [4], wherein
[0035] In the solid electrolyte, the ratio of the content of the water to the content of the metal oxide is 1 to 12 in terms of molar ratio.
[0036] [6]
[0037] The electrode composition for an all-solid-state secondary battery according to any one of [1] to [5], wherein
[0038] In the solid electrolyte, the content of the metal salt relative to the amount of the metal oxide is 0.001 to 1.5 in terms of molar ratio.
[0039] 〔7〕
[0040] An electrode sheet for an all-solid-state secondary battery having an active material layer formed using the electrode composition for an all-solid-state secondary battery described in any one of [1] to [6].
[0041] [8]
[0042] An all-solid-state secondary battery is composed of a positive electrode active material layer, a solid electrolyte layer and a negative electrode active material layer in sequence, wherein:
[0043] At least one of the positive electrode active material layer and the negative electrode active material layer is an active material layer formed using the electrode composition for an all-solid-state secondary battery according to any one of [1] to [6].
[0044] 〔9〕
[0045] A method for manufacturing an electrode sheet for an all-solid-state secondary battery comprises the following steps:
[0046] An active material layer is formed using the electrode composition for an all-solid-state secondary battery described in any one of [1] to [6].
[0047] 〔10〕
[0048] A method for manufacturing an all-solid-state secondary battery, wherein the all-solid-state secondary battery is sequentially configured with a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer, and the method for manufacturing the all-solid-state secondary battery comprises the following steps:
[0049] At least one of the positive electrode active material layer and the negative electrode active material layer is formed using the electrode composition for an all-solid-state secondary battery described in any one of [1] to [6].
[0050] In the present invention or the specification, a numerical range expressed using "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit.
[0051] Effects of the Invention
[0052] The electrode composition for all-solid-state secondary batteries of the present invention, even as a high-concentration slurry, can form an active material layer with excellent dispersion stability of the dispersion medium and not prone to cracking and peeling. Therefore, when used to manufacture an electrode sheet for all-solid-state secondary batteries and an all-solid-state secondary battery, the drying process can be shortened, thereby further improving productivity. The energy loss of the all-solid-state secondary battery having an active material layer formed using the electrode composition for all-solid-state secondary batteries is small, thereby further achieving high lifespan. According to the manufacturing method of the electrode sheet for all-solid-state secondary batteries of the present invention, the above-mentioned electrode sheet for all-solid-state secondary batteries of the present invention can be obtained. In addition, according to the manufacturing method of the all-solid-state secondary battery of the present invention, the above-mentioned all-solid-state secondary battery of the present invention can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 It is a cross-sectional view schematically showing an example of the structure of an all-solid-state lithium-ion secondary battery.
[0054] Figure 2 This is a diagram showing an example of an X-ray diffraction pattern for explaining the X-ray diffraction characteristics of the solid electrolyte (II) used in the present invention.
[0055] Figure 3 This is a diagram showing an example of the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of the solid electrolyte (II) used in the present invention.
[0056] Figure 4 The solid electrolyte (II) used in the present invention is solidified at 20°C or 120°C. 7A diagram showing an example of a spectrum obtained during Li-NMR measurement.
[0057] Figure 5 It means that the solid state of lithium tetraborate crystals is carried out at 20℃ or 120℃ 7 A diagram showing an example of a spectrum obtained during Li-NMR measurement.
[0058] Figure 6 The solid electrolyte (II) used in the present invention is solidified at 20°C. 7 A diagram showing an example of a spectrum obtained during Li-NMR measurement.
[0059] Figure 7 Yes Figure 6 Figure 2 shows the peak waveform separation.
[0060] Figure 8 This is a diagram showing an example of the Raman spectrum of the solid electrolyte (II) used in the present invention.
[0061] Fig. 9 This is a diagram showing the Raman spectrum of lithium tetraborate crystals.
[0062] Fig.10 Graph showing the reduced two-body distribution function G(r) obtained by total X-ray scattering measurement of powdered Li2B4O7 crystals.
[0063] Fig.11 This is a diagram showing the X-ray diffraction pattern of powdered Li2B4O7 crystals. DETAILED DESCRIPTION
[0064] [Electrode composition for all-solid-state secondary batteries]
[0065] The electrode composition for an all-solid-state secondary battery of the present invention (hereinafter, also referred to as "the electrode composition of the present invention") comprises a solid electrolyte and an active material in an amorphous state. The solid electrolyte is a solid particle-shaped electrolyte comprising a metal oxide containing at least one of an alkali metal element and an alkaline earth metal element and an oxygen element, at least one of an alkali metal salt and an alkaline earth metal salt, and water. In the electrode composition of the present invention, the ratio (M / N) of the median diameter M of the active material to the median diameter N of the above-mentioned solid electrolyte is controlled to be 0.05≤M / N<1.2.
[0066] The electrode composition of the present invention can be preferably used to form an active material layer in an all-solid-state secondary battery.
[0067] In the electrode composition of the present invention, the solid electrolyte has a specific composition, is in an amorphous state, and shows a high physical property of flexibility that is relatively easy to undergo plastic deformation. In addition, by further controlling the relationship between the median diameters of the solid electrolyte and the active material so that it satisfies the above ratio, even if the electrode composition of the present invention is used as a high-concentration slurry, the stability of the dispersion medium can be excellent. In addition, in the active material layer formed, the solid electrolyte also plays a role like a binder and can improve the adhesion of the solid particles to each other, and the flexibility is also excellent. In this way, by using the electrode composition of the present invention, even if a sulfide-based solid electrolyte is not used as a solid electrolyte, and a binder such as an organic polymer is not used, an active material layer with high flexibility can be formed.
[0068] The ratio M / N is preferably 0.1≤M / N≤1.1, more preferably 0.3≤M / N≤1.0, further preferably 0.4≤M / N≤0.8, and particularly preferably 0.45≤M / N≤0.7.
[0069] In the electrode composition of the present invention, the ratio of the solid electrolyte content to the active material content is preferably solid electrolyte:active material = 20:80 to 80:20, more preferably 20:80 to 50:50, and further preferably 25:75 to 40:60. Solid electrolyte:active material = 40:60 to 60:40 in terms of mass ratio.
[0070] <Solid electrolyte>
[0071] The solid electrolyte constituting the electrode composition of the present invention is in an amorphous state (same meaning as non-crystalline state or amorphous state), and includes a metal oxide containing at least one of an alkali metal element and an alkaline earth metal element and an oxygen element, at least one of an alkali metal salt and an alkaline earth metal salt, and water. (Hereinafter, the solid electrolyte is also referred to as "solid electrolyte (I)".) The solid electrolyte (I) is generally an inorganic solid electrolyte.
[0072] Solid electrolyte (I) is in an amorphous state and shows elastic properties that are prone to plastic deformation. As a result, in a layer including a solid electrolyte (I) formed by a pressurized treatment, the adhesion between solid electrolytes (I) and / or the adhesion between solid electrolytes (I) and components (e.g., active materials) present in other structural layers is improved, and the interface resistance can be reduced, thereby obtaining more excellent ion conductivity. By using the solid electrolyte (I), although it is an oxide-based solid electrolyte with high safety, even if a high-temperature sintering process is not performed, it is possible to form a structural layer, etc., by pressurized treatment, etc., to an ion conductor showing excellent ion conductivity, an all-solid-state secondary battery.
[0073] In the present invention, the solid electrolyte (I) being in an "amorphous state" means that it has a broad scattering band having a vertex in the region of 2θ values of 20° to 40° by X-ray diffraction using CuKα rays, and may have crystalline diffraction lines.
[0074] The median diameter N of the solid electrolyte (I) is not particularly limited as long as it becomes the above M / N, preferably 5 to 50 μm, more preferably 5 to 25 μm, and more preferably 5 to 20 μm. The method for measuring the above median diameter (D50) is as follows: the particle image is obtained by flow particle image analysis and the particle size distribution is calculated, and the obtained distribution is analyzed. In addition, the above particle size corresponds to the equivalent circle diameter.
[0075] The method for controlling the median diameter is not particularly limited, and for example, the median diameter can be controlled by pulverizing the particles by a mechanical milling treatment described later and then sieving.
[0076] -water-
[0077] The water contained in the solid electrolyte (I) at least includes bound water. Although the reason why the solid electrolyte (I) exhibits high lithium ion conductivity is not clear, in the amorphous solid electrolyte (I), a soft hydration layer is easily formed on the surface containing the metal oxide, and a large amount of metal derived from the metal salt is contained in the hydration layer, and as a result, it is believed that the ion conductivity is further improved.
[0078] Here, in the present invention or the specification, "bound water" refers to water other than water existing as free water or OH groups bonded to metal oxides. Even if the solid electrolyte (I) contains water, it is in the state of solid particles (including the state in which the solid particles are bonded to each other) and functions as a solid electrolyte of an all-solid-state secondary battery. That is, the solid electrolyte (I) contains bound water that is not removed or difficult to remove under normal drying conditions. In addition, as long as the solid electrolyte (I) functions as a solid electrolyte of an all-solid-state secondary battery in the state of solid particles (a state that can be processed in the state of powder), the solid electrolyte (I) may contain free water. That is, in the present invention, if the solid electrolyte can be treated as a solid particle (solid powder), the "electrode composition" also includes a mode in which the solid electrolyte contains water. And, for example, the solid electrolyte (I) in which the ratio of the content of water described later to the content of the metal oxide is less than 12 in molar ratio is not in any state of paste and gel, but in the state of solid particles (solid powder).
[0079] In the solid electrolyte (I), from the viewpoint of further improving ion conductivity, the ratio of the water content to the metal oxide content (water / metal oxide) is preferably controlled to be 1 to 12 in terms of molar ratio, more preferably 2 to 12, and further preferably 3 to 11. Furthermore, the molar ratio is also preferably 2 to 10, also preferably 2 to 8, also preferably 2 to 7, and also preferably 3 to 7.
[0080] -Containing metal oxides-
[0081] Examples of the alkali metal element or alkaline earth metal element contained in the metal oxide include Li, Na, K, Rb, Cs, Fr, Ca, Sr, Ba and Ra, preferably Li or Na, and more preferably Li.
[0082] The metal-containing oxide preferably contains at least one of alkali metal elements and alkaline earth metal elements and oxygen, and further contains typical elements other than these. Typical elements include B, C, N, F, Si, P, S, Cl, As, Se, Br, Te and I, preferably B.
[0083] A preferred embodiment of the metal-containing oxide is a lithium-containing oxide containing Li, B, and O (hereinafter, also simply referred to as “lithium-containing oxide”).
[0084] -Alkali metal salts and alkaline earth metal salts-
[0085] Alkali metal salts and alkaline earth metal salts (hereinafter also referred to as metal salts) are not particularly limited as long as they are salts of alkali metals or alkaline earth metals. For example, salts of alkali metals or alkaline earth metals include salts composed of alkali metal cations or alkaline earth metal cations and anions.
[0086] Examples of alkali metals of alkali metal salts and alkaline earth metals of alkaline earth metal salts include Li, Na, K, Rb, Cs, Fr, Ca, Sr, Ba and Ra, preferably Li or Na, more preferably Li. The alkali metal element or alkaline earth metal element in the metal-containing oxide contained in the electrode composition of the present invention may be the same as or different from the alkali metal element or alkaline earth metal element in the metal salt contained in the electrode composition of the present invention.
[0087] The anion of the alkali metal or alkaline earth metal salt of the alkali metal salt is preferably an organic anion, and more preferably an organic anion having a halogen atom. Specific examples of the anion include Cl - Br - ,I - 、SO4 2- 、NO3 - 、CO3 2- 、CH3COO - PF6- 、BF4 - 、AsF6 - 、SbF6 - 、ClO4 - BrO4 - IO4 - 、AlCl4 - CF3SO3 - 、(CF3SO2)2N - 、(CF3CF2SO2)2N - 、(FSO2)2N - 、(CF3SO2)(C4F9SO2)N - 、(CF3SO2)3C - 、[PF5(CF2CF2CF3)] - 、[PF4(CF2CF2CF3)2 - ], [PF3(CF2CF2CF3)3] - 、[PF5(CF2CF2CF2CF3)] - 、[PF4(CF2CF2CF2CF3)2] - 、[PF3(CF2CF2CF2CF3)3] - , sodium bis(oxalate)borate anion, difluorooxalate borate anion, etc., preferably Br - ,I - CF3SO3 - 、(CF3SO2)2N - 、(CF3CF2SO2)2N - 、(FSO2)2N - 、(CF3SO2)(C4F9SO2)N - 、(CF3SO2)3C - 、[PF5(CF2CF2CF3)] - 、[PF4(CF2CF2CF3)2 - ], [PF3(CF2CF2CF3)3] - 、[PF5(CF2CF2CF2CF3)] - 、[PF4(CF2CF2CF2CF3)2] - 、[PF3(CF2CF2CF2CF3)3] - , more preferably (CF3SO2)2N - 、(CF3CF2SO2)2N - 、(FSO2)2N - 、(CF3SO2)(C4F9SO2)N - .
[0088] In the solid electrolyte (I), the ratio of the content of the above-mentioned metal salt to the content of the above-mentioned metal oxide (metal salt / metal oxide) is preferably 0.001 to 1.5 in terms of molar ratio, more preferably 0.001 to 1.2, further preferably 0.01 to 1.2, particularly preferably 0.1 to 1.2, and most preferably 0.5 to 1.2.
[0089] The solid electrolyte (I) is preferably an embodiment in which the metal oxide is a lithium-containing oxide containing Li, B and O, and the metal salt is a lithium salt. This preferred embodiment of the solid electrolyte (I) is also referred to as a solid electrolyte (II).
[0090] Hereinafter, the present invention will be described by taking an embodiment using the solid electrolyte (II) as an example, but the present invention is not limited to the embodiment described below except for those specified in the present invention.
[0091] In the present invention, when the solid electrolyte (II) is in an "amorphous state", it preferably satisfies the following X-ray diffraction characteristics. That is, when the solid electrolyte (II) satisfies the following X-ray diffraction characteristics, the solid electrolyte (II) is in an "amorphous state".
[0092] (X-ray diffraction characteristics)
[0093] In the X-ray diffraction pattern of the solid electrolyte (II) obtained from X-ray diffraction measurement using CuKα rays, there is no first peak whose peak top is located in the range of diffraction angle 2θ of 21.6 to 22.0° and whose full width at half maximum is 0.65° or less, no second peak whose peak top is located in the range of diffraction angle 2θ of 25.4 to 25.8° and whose full width at half maximum is 0.65° or less, no third peak whose peak top is located in the range of diffraction angle 2θ of 33.4 to 33.8° and whose full width at half maximum is 0.65° or less, and no fourth peak whose peak top is located in the range of diffraction angle 2θ of 34.4 to 34.8° and whose full width at half maximum is 0.65° or less, or
[0094] In the X-ray diffraction pattern, when at least one of the above-mentioned 1st peak, 2nd peak, 3rd peak and 4th peak (hereinafter referred to as "peak X") is present, the intensity ratio of at least one of the peaks X calculated by the intensity measurement method described below is 5.0 or less.
[0095] - Strength measurement method -
[0096] The arithmetic mean of Av1 and Av2 is calculated by calculating the average intensity (Av1) in the range of +0.45° to +0.55° from the diffraction angle 2θ of the peak top of the peak X, and calculating the average intensity (Av2) in the range of -0.55° to -0.45° from the diffraction angle 2θ of the peak top of the peak X. The ratio of the peak intensity at the peak top of the peak X to the arithmetic mean (peak intensity at the peak top of the peak X / arithmetic mean) is taken as the intensity ratio.
[0097] The X-ray diffraction characteristics will be described in more detail.
[0098] In the X-ray diffraction pattern obtained from the X-ray diffraction measurement of the solid electrolyte (II) using CuKα rays, when the above-mentioned first peak, second peak, third peak and fourth peak do not exist, the above-mentioned X-ray diffraction characteristics are satisfied and the solid electrolyte (II) is in an amorphous state.
[0099] Furthermore, in the X-ray diffraction pattern of the solid electrolyte (II) obtained from the X-ray diffraction measurement using CuKα rays, when the above-mentioned peak X is present, when the intensity ratio of at least one peak among the peaks X obtained by the above-mentioned intensity measurement method also satisfies 5.0 or less, the above-mentioned X-ray diffraction characteristics are also satisfied, and the solid electrolyte (II) is in an amorphous state.
[0100] Here, the full width at half maximum (FWHM) of the peak refers to the peak width (°) at a point where the peak intensity at the top of the peak is 1 / 2.
[0101] refer to Figure 2 , the above-mentioned intensity measurement method is explained in more detail.
[0102] Figure 2 This is a diagram showing an example of a peak X appearing in a diffraction pattern obtained from X-ray diffraction measurement using CuKα rays of a solid electrolyte (II). Figure 2 In the diffraction pattern shown, the intensity of the peak top is shown to show a specific peak with an intensity of 1. In the intensity measurement method, as Figure 2 As shown, the average intensity (Av1) in the range of +0.45° to +0.55° is calculated from the diffraction angle 2θ of the peak top of the peak X, and the average intensity (Av2) in the range of -0.55° to -0.45° is calculated from the diffraction angle 2θ of the peak top of the peak X. Next, the arithmetic mean of Av1 and Av2 is calculated, and the ratio of intensity 1 to the arithmetic mean is obtained as the intensity ratio. The situation where the above-mentioned X-ray diffraction characteristics are satisfied means that there is no crystal structure or almost no crystal structure in the solid electrolyte (II) and it is in an amorphous state.
[0103] That is, the above-mentioned 1st peak to 4th peak are peaks mainly derived from the crystal structure (for example, the crystal structure of lithium tetraborate) in the solid electrolyte, and the absence of these peaks means that it is in an amorphous state. And, even in the case where there is at least one peak in the 1st peak to the 4th peak, the intensity ratio of at least one peak in the peak X that exists is 5.0 or less, which means that in the solid electrolyte (II), there is almost no crystal structure that hinders the effect of the present invention. In addition, for example, the peak derived from a specific component (for example, a lithium salt) sometimes overlaps with any one of the above-mentioned 1st peak to the 4th peak. However, in a solid electrolyte in an amorphous state, the 1st peak to the 4th peak usually decreases, so even if it is assumed that the peak caused by the above-mentioned specific component coincidentally overlaps with any one of the 1st peak to the 4th peak to appear a large peak, there is at least one peak X with an intensity ratio below a specified value, which can be said to indicate that the solid electrolyte (II) is in an amorphous state.
[0104] The above X-ray diffraction measurement was performed using CuKα rays and under the measurement conditions of 0.01° / step, 3° / minute.
[0105] In the X-ray diffraction pattern of the solid electrolyte (II) obtained from the X-ray diffraction measurement using CuKα rays, even if none of the above-mentioned first peak, second peak, third peak and fourth peak exists, or at least one peak X among the above-mentioned first peak, second peak, third peak and fourth peak exists, it is preferred that the intensity ratio of at least one peak X is 3.0 or less.
[0106] Among them, even if the above-mentioned first peak, second peak, third peak and fourth peak do not exist, or at least one peak X among the above-mentioned first peak, second peak, third peak and fourth peak exists, it is preferred that the intensity ratio of at least one peak X is less than 2.0.
[0107] In addition, in the above-mentioned X-ray diffraction spectrum, when there are two or more peaks with peak tops in the range of 21.6 to 22.0° and a half-width of 0.65° or less, the peak with the largest diffraction X-ray intensity is selected as the first peak to determine the above-mentioned X-ray diffraction characteristics.
[0108] Furthermore, in the above-mentioned X-ray diffraction pattern, when there are two or more peaks with peak tops in the range of 25.4 to 25.8° and a full width at half maximum of less than 0.65°, the peak with the largest diffraction X-ray intensity is selected as the second peak to perform the above-mentioned X-ray diffraction characteristics.
[0109] Furthermore, in the above-mentioned X-ray diffraction spectrum, when there are two or more peaks with peak tops in the range of 33.4 to 33.8° and a half-width of less than 0.65°, the peak with the largest diffraction X-ray intensity is selected as the third peak to determine the above-mentioned X-ray diffraction characteristics.
[0110] Furthermore, in the above-mentioned X-ray diffraction spectrum, when there are two or more peaks with peak tops in the range of 34.4 to 34.8° and a half-width of less than 0.65°, the peak with the largest diffraction X-ray intensity is selected as the fourth peak to determine the above-mentioned X-ray diffraction characteristics.
[0111] (Total X-ray Scattering Properties)
[0112] The solid electrolyte (II) preferably satisfies the following requirement A-1 as the total X-ray scattering property. When the solid electrolyte (II) satisfies the above-mentioned X-ray diffraction property, the solid electrolyte (II) usually satisfies the following requirement A-2.
[0113] - Requirement A-1-
[0114] In the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of solid electrolyte (II), there is a peak located at r The first peak and the peak top in the range of r are The second peak in the range of , the peak G(r) of the first peak shows more than 1.0, and the peak G(r) of the second peak shows more than 0.8.
[0115] - Requirement A-2-
[0116] In the reduced two-body distribution function G(r) obtained from total X-ray scattering measurements of solid electrolytes (II), and The absolute value of G(r) in the following range is less than 1.0.
[0117] When the solid electrolyte (II) satisfies requirements A-1 and A-2, it has a short-range ordered structure related to the interatomic distance of BO and BB, but has almost no long-range ordered structure, so the oxide solid electrolyte itself shows elastic properties that are softer and more susceptible to plastic deformation than conventional lithium-containing oxides. As a result, it is speculated that in the layer containing the solid electrolyte (II) formed by pressure treatment, the adhesion between the solid electrolytes (II) and / or the adhesion between the solid electrolyte (II) and other ion conductors (e.g., active materials) is improved, the interface resistance can be reduced, and thus better ion conductivity can be obtained.
[0118] The requirements A-1 and A-2 will be described in more detail with reference to the drawings.
[0119] Figure 3 An example of the reduced two-body distribution function G(r) obtained by total X-ray scattering measurement of the solid electrolyte (II) is shown. Figure 3 The vertical axis is the reduced two-body distribution function obtained by Fourier transform of X-ray scattering, which represents the probability of the existence of an atom at a distance r. The total X-ray scattering measurement can be performed by SPring-8BL04B2 (acceleration voltage 61.4keV, wavelength ) is performed. The scattering intensity I obtained by the experiment obs The transformation is performed according to the following steps to obtain the reduced two-body distribution function G(r).
[0120] First, the scattering intensity I obs It is expressed by the following equation (1). And, as shown in the following equation (2), the structure factor S(Q) (Q: scattering vector) is obtained by dividing the coherent scattering I coh It is obtained by dividing by the product of the number of atoms N and the square of the atomic scattering factor f.
[0121] I obs =I coh +I incoh +I 荧光 (1)
[0122] [Formula 1]
[0123]
[0124] The structure factor S(Q) is used in PDF (Pair Distribution Function) analysis. In the above equation (2), the required intensity is only the coherent scattering I coh . Incoherent scattering I incoh and Fluorescent X-ray I 荧光 can be used to subtract the theoretical formula using a blank measurement and the detector's discriminator from the scattered intensity I obs Minus.
[0125] Coherent Scattering I coh It is expressed by Debye's scattering formula (the following formula (3)) (N: total number of atoms, f: atomic scattering factor, r ij : the interatomic distance between ij).
[0126] [Formula 2]
[0127]
[0128] If we focus on any atom and let the atomic density at a distance r be ρ(r), then the number of atoms existing in a sphere with a radius of r-r+d(r) is 4πr. 2 ρ(r)dr, the above formula (3) is expressed by the following formula (4).
[0129] [Formula 3]
[0130]
[0131] If the average density of atoms is set to ρ0 and the above formula (4) is modified, the following formula (5) can be obtained.
[0132] [Formula 4]
[0133]
[0134] The following formula (6) can be obtained from the above formula (5) and formula (2).
[0135] [Formula 5]
[0136]
[0137] The two-body distribution function g(r) is expressed by the following equation (7).
[0138] [Formula 6]
[0139]
[0140] The following formula (8) can be obtained from the above formula (6) and formula (7).
[0141] [Formula 7]
[0142]
[0143] As described above, the two-body distribution function can be obtained by Fourier transforming the structure factor S(Q). In order to easily observe the medium-range order / long-range order, the two-body distribution function g(r) is converted into the function of the formula: G(r) = 4πr(g(r)-1) to reduce the two-body distribution function G(r) ( Figure 3 ). g(r) oscillating around 0 represents the density difference from the average density at each interatomic distance, and when there is a correlation at a specific interatomic distance, the average density becomes higher than 1. Therefore, the distance and coordination number of the element corresponding to the local to the intermediate distance are reflected. If the order disappears, ρ(r) approaches the average density, so g(r) gradually approaches 1. Therefore, in an amorphous structure, since the larger r becomes, the more the order disappears, g(r) becomes 1, that is, G(r) becomes 0.
[0144] In Element A-1, if Figure 3 As shown, in the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of the solid electrolyte (II), there is a peak located at r The first peak P1 and the peak top are located at r within the range of In the second peak P2 within the range of , the peak G(r) of the first peak P1 shows a value greater than 1.0 (preferably greater than 1.2), and the peak G(r) of the second peak P2 shows a value greater than 0.8 (preferably greater than 1.0).
[0145] In addition, Figure 3 The peak of the first peak P1 is located at The peak of the second peak P2 is located at
[0146] exist There is a peak at the position of B (boron)-O (oxygen) interatomic distance. There is a peak at the position of the interatomic distance attributed to B (boron)-B (boron). That is, the observation of the above two peaks (the first peak and the second peak) means that a periodic structure corresponding to the above two interatomic distances exists in the solid electrolyte (II).
[0147] Furthermore, in Element A-2, if Figure 3 As shown, when r is more than and In the following range, the absolute value of G(r) is less than 1.0. As mentioned above, when r is greater than and The case where the absolute value of G(r) in the following range is less than 1.0 means that there is almost no long-range ordered structure in the solid electrolyte (II).
[0148] In addition, in the above-mentioned reduced two-body distribution function G(r), when r is In the following range, there are peaks other than the first peak and other than the second peak.
[0149] A method for making the solid electrolyte (II) into an amorphous state will be described. The solid electrolyte (I) can also be made into an amorphous state by the same method.
[0150] The method for making the solid electrolyte (II) into an amorphous state is not particularly limited. For example, there is the following method: in the preparation of the solid electrolyte (II), a lithium-containing oxide that has been subjected to a mechanical grinding treatment is used as a raw material of the lithium-containing oxide. The mechanical grinding treatment can also be performed in the presence of a lithium salt.
[0151] -Mechanical grinding treatment-
[0152] Mechanical grinding treatment refers to a process of pulverizing a sample while imparting mechanical energy to the sample. As a mechanical grinding treatment, for example, grinding treatment using a ball mill, a vibration mill, a turbine mill or a disc mill can be cited. From the viewpoint of obtaining amorphous solid electrolyte (II) with good productivity, grinding treatment using a ball mill is preferred. As a ball mill, for example, a vibration ball mill, a rotary ball mill and a planetary ball mill can be cited, and a planetary ball mill is more preferred.
[0153] The conditions of the ball milling treatment can be appropriately adjusted according to the treatment object. The material of the grinding ball (medium) is not particularly limited, for example, agate, silicon nitride, zirconium oxide, aluminum oxide and iron alloys can be cited, preferably yttria stabilized zirconia (YSZ). The average particle size of the grinding balls is not particularly limited. From the viewpoint of being able to manufacture solid electrolytes (II) with good productivity, it is preferably 1 to 10 mm, and more preferably 3 to 7 mm. The above average particle size is the value obtained by randomly measuring the diameters of 50 grinding balls and arithmetically averaging these. In the case where the grinding balls are not spherical, the major diameter is set as the diameter. The number of grinding balls is not particularly limited, and 10 to 100 are usually used, and preferably 40 to 60 are used for ball milling.
[0154] The material of the pulverizing pot in the ball milling treatment is not particularly limited, and examples thereof include agate, silicon nitride, zirconium oxide, aluminum oxide, and iron-based alloys, and yttria-stabilized zirconia (YSZ) is preferred.
[0155] The rotation speed of the ball milling process is not particularly limited, and can be set to 200 to 700 rpm, preferably 350 to 550 rpm. The treatment time of the ball mill is not particularly limited, and can be set to 10 to 200 hours, preferably 20 to 140 hours. The atmosphere of the ball milling process can be the atmosphere or an inert gas (e.g., argon, helium, nitrogen, etc.) atmosphere.
[0156] In the production of the solid electrolyte (II), the following steps 1A to 3A are preferably performed.
[0157] Step 1A: A step of mechanically grinding a lithium-containing oxide in the presence of a lithium salt
[0158] Step 2A: Step of mixing the product obtained in step 1A with water
[0159] Step 3A: A step of removing water from the dispersion obtained in step 2A to obtain a solid electrolyte (II)
[0160] In step 1A, the amount of the lithium salt used is not particularly limited and can be appropriately adjusted to obtain the solid electrolyte (II) specified in the present invention.
[0161] In the above step 2A, the amount of water used is not particularly limited. For example, the amount of water used can be 10 to 200 parts by mass, preferably 50 to 150 parts by mass, based on 100 parts by mass of the product obtained in step 1A.
[0162] The method of mixing the product obtained in step 1A and water is not particularly limited, and they can be mixed together or water can be added to the product obtained in step 1A in stages for mixing. During mixing, ultrasonic treatment can be performed as needed. The time of ultrasonic treatment is not particularly limited, and can be set to 10 minutes to 5 hours, for example.
[0163] Step 3A is a step of removing water from the dispersion obtained in step 2A to obtain solid electrolyte (II). The method of removing water from the dispersion obtained in step 2A is not particularly limited, and water may be removed by heating treatment or by vacuum drying treatment.
[0164] The drying conditions are not particularly limited, and examples thereof include the drying conditions used in the Examples.
[0165] Prior to the step 1A, a step 0 of subjecting the lithium-containing oxide to mechanical milling in an environment without the presence of a lithium salt may be performed.
[0166] In the production of the solid electrolyte (II), it is also preferable to perform the following steps 1B to 3B instead of the above steps 1A to 3A.
[0167] Step 1B: Mechanical grinding of lithium-containing oxide
[0168] Step 2B: Step of mixing the product obtained in step 1B, water and lithium salt
[0169] Step 3B: A step of removing water from the dispersion obtained in step 2B to obtain a solid electrolyte (II)
[0170] The difference between step 1B and step 1A is that in step 1A, the mechanical milling treatment is carried out in the presence of a lithium salt, whereas in step 1B, the mechanical milling treatment is carried out without using a lithium salt. Therefore, in step 2B, the product obtained in step 1B, water, and a lithium salt are mixed.
[0171] The steps of step 2B are not particularly limited, and may be a method of mixing the product obtained in step 1B, water, and a lithium salt all together (method 1), a method of mixing the product obtained in step 1B and water to prepare a dispersion, and then mixing the obtained dispersion with a lithium salt (method 2), or a method of mixing the product obtained in step 1B and water to prepare a dispersion 1, mixing a lithium salt and water to prepare a solution 2, and then mixing the dispersion 1 and the solution 2 (method 3). When mixing the product obtained in step 1B and water, a dispersion treatment such as an ultrasonic treatment may be appropriately performed.
[0172] In method 2, when the dispersion obtained by mixing the product obtained in step 1B and water and the lithium salt are mixed, if there is too much lithium salt, the obtained liquid is easily gelled, and the mixing amount of the lithium salt is limited. In contrast, in method 3, even if the product obtained in step 1B and the lithium salt are mixed in approximately equimolar amounts, gelation of the dispersion is not likely to occur, and the mixing amount of the lithium salt can be further increased. From this point of view, method 3 is preferred.
[0173] Step 3B is the same as step 3A.
[0174] In the production of the solid electrolyte (II), it is also preferable to perform the following steps 1C to 3C instead of the above steps 1A to 3A.
[0175] Step 1C: Step of mechanically grinding the lithium-containing oxide
[0176] Step 2C: Step of mixing the product obtained in step 1C with water
[0177] Step 3C: A step of mixing a product obtained by removing water from the dispersion obtained in step 2C with a lithium salt to obtain a solid electrolyte (II)
[0178] Step 1C is the same as step 1B.
[0179] Step 2C is the same as step 2A.
[0180] Step 3C is different from Steps 3A and 3B in that a product obtained by removing water from the dispersion obtained in Step 2C and a lithium salt are mixed.
[0181] In step 3C, the amount of the lithium salt used is not particularly limited and can be appropriately adjusted to obtain the solid electrolyte (II) specified in the present invention.
[0182] The method of mixing the product obtained by removing water from the dispersion obtained in step 2C and the lithium salt is not particularly limited, and may be a method of immersing a solution obtained by dissolving the lithium salt in water in the product and mixing the two.
[0183] (Composition of Solid Electrolyte (II))
[0184] As described above, the solid electrolyte (II) used in the present invention is an amorphous solid electrolyte, and the solid electrolyte (II) contains a lithium oxide, a lithium salt, and water.
[0185] The molar ratio of the water content in the solid electrolyte (II) to the lithium-containing oxide content is preferably 1 to 12, more preferably 2 to 12, and further preferably 3 to 11. Furthermore, the molar ratio is preferably 2 to 10, 2 to 8, 2 to 7, and 3 to 7.
[0186] The ratio of the content of the lithium salt in the solid electrolyte (II) to the content of the lithium-containing oxide is preferably 0.001 to 1.5, more preferably 0.001 to 1.2, further preferably 0.01 to 1.2, particularly preferably 0.1 to 1.2, and most preferably 0.5 to 1.2 in terms of molar ratio.
[0187] In the solid electrolyte (II), the content of the lithium salt is 0.001 to 1.5 in molar ratio relative to the content of the lithium-containing oxide, and the content of water is 1 to 12 in molar ratio relative to the content of the lithium-containing oxide.
[0188] The molar amount of lithium-containing oxide, lithium salt and water in the solid electrolyte (II) can be determined by elemental analysis. As elemental analysis, for example, the elemental analysis method described in the elemental composition of the solid electrolyte (II) described later can be cited. In addition, the molar amount of water can also be determined by the Karl Fischer method, etc.
[0189] The water content in the solid electrolyte (II) is preferably 50% by mass or less, more preferably 45% by mass or less, further preferably 40% by mass or less, and particularly preferably 35% by mass or less. In addition, the water content in the solid electrolyte (II) is also preferably 30% by mass or less, and also preferably 25% by mass or less.
[0190] And, the content of water in the solid electrolyte (II) is usually 5% by mass or more, preferably 10% by mass or more, and preferably 15% by mass or more. Therefore, the content of water in the solid electrolyte (II) is preferably 5 to 50% by mass, more preferably 5 to 45% by mass, further preferably 10 to 40% by mass, further preferably 10 to 35% by mass, also preferably 10 to 30% by mass, also preferably 15 to 30% by mass, and also preferably 15 to 25% by mass.
[0191] The content of the lithium-containing oxide in the solid electrolyte (II) is preferably 20 to 80% by mass, more preferably 20 to 75% by mass, and still more preferably 25 to 70% by mass.
[0192] The content of the lithium salt in the solid electrolyte (II) is preferably 0.5 to 60% by mass, more preferably 1.0 to 55% by mass, further preferably 2.0 to 50% by mass, and still more preferably 5.0 to 50% by mass.
[0193] -Containing lithium oxide-
[0194] As described above, the lithium-containing oxide constituting the solid electrolyte (II) contains Li, B, and O.
[0195] The lithium-containing oxide is preferably composed of Li 2+x B 4+y O 7+z (-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3). That is, when the molar amount of B is set to 4.00 to represent the molar amount of Li, the molar amount of Li is preferably 1.58 to 2.49 (i.e., 1.7×4 / 4.3 to 2.3×4 / 3.7), and the molar amount of O is 6.23 to 7.89 (i.e., 6.7×4 / 4.3 to 7.3×4 / 3.7). In other words, when the molar content of B is set to 4.00, the relative value of the molar content of Li is preferably 1.58 to 2.49, and the molar amount of O is 6.23 to 7.89. As such a lithium-containing oxide, typically lithium tetraborate (Li2B4O7) can be cited.
[0196] Furthermore, the lithium-containing oxide is preferably composed of Li 1+x B 3+y O 5+z (-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3). Such lithium-containing oxides typically include lithium triborate (LiB3O5).
[0197] Furthermore, the lithium-containing oxide is preferably composed of Li 3+x B 11+y O 18+z (-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3) is a compound represented by (-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3). As such lithium-containing oxides, Li3B 11 O 18 .
[0198] Furthermore, the lithium-containing oxide is preferably composed of Li 3+x B 7+y O 12+z (-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3). As such lithium-containing oxides, Li3B7O is typically mentioned. 12 .
[0199] Therefore, the lithium-containing oxide is preferably the Li 2+x B 4+y O 7+z , the above Li 1+x B 3+y O 5+z , Li 3+x B 11+y O 18+z Li 3+x B 7+y O 12+z At least one of the following.
[0200] Furthermore, LiBO5, Li2B7O 12 , LiB2O3(OH)H2O and Li4B8O 13 At least one of (OH)2(H2O)3 and the like is used as the lithium-containing oxide.
[0201] In the solid electrolyte (II), the lithium-containing oxide is preferably in an amorphous state. That is, the lithium-containing oxide in the solid electrolyte (II) is preferably also in a desired amorphous state so that the solid electrolyte (II) is in the above-mentioned amorphous state.
[0202] Among them, the lithium-containing oxide is preferably lithium tetraborate in an amorphous state.
[0203] -Lithium salts-
[0204] The lithium salt constituting the solid electrolyte (II) used in the present invention is not particularly limited, and examples thereof include Li + and anions, preferably Li + and an organic anion, more preferably a salt composed of Li + And salts composed of organic anions having halogen atoms.
[0205] The lithium salt constituting the solid electrolyte (II) used in the present invention preferably contains two or more elements selected from the group consisting of elements of Group 3 of the periodic table, elements of Group 4 of the periodic table, elements of Group 13 of the periodic table, elements of Group 14 of the periodic table, elements of Group 15 of the periodic table, elements of Group 16 of the periodic table, elements of Group 17 of the periodic table and H.
[0206] As the lithium salt constituting the solid electrolyte (II) used in the present invention, for example, a compound represented by the following formula (1) is preferable.
[0207] Formula (1) LiN(R f1 SO2)(R f2 SO2)
[0208] R f1 and Rf2 Each independently represents a halogen atom or a perfluoroalkyl group.
[0209] R f1 and R f2 In the case of a perfluoroalkyl group, the number of carbon atoms in the perfluoroalkyl group is not particularly limited.
[0210] R f1 and R f2 It is preferably a halogen atom or a perfluoroalkyl group having 1 to 6 carbon atoms, more preferably a halogen atom or a perfluoroalkyl group having 1 to 2 carbon atoms, and still more preferably a halogen atom. If the volume of the terminal group increases, the steric hindrance increases, which becomes a factor that hinders ion conduction. Therefore, R f1 and R f2 In the case of a perfluoroalkyl group, the one having a smaller number of carbon atoms is preferred.
[0211] The lithium salt that can be contained in the solid electrolyte (II) used in the present invention is not limited to the compound represented by the above formula (1). The lithium salt that can be contained in the solid electrolyte (II) used in the present invention is exemplified below.
[0212] (L-1) Inorganic lithium salts: inorganic fluoride salts such as LiPF6, LiBF4, LiAsF6 and LiSbF6; perhalide salts such as LiClO4, LiBrO4 and LiIO4; inorganic chloride salts such as LiAlCl4.
[0213] (L-2) Fluorine-containing organic lithium salts: perfluoroalkyl sulfonates such as LiCF3SO3; fluorosulfonyl imide salts or perfluoroalkyl sulfonyl imide salts such as LiN(CF3SO2)2, LiN(CF3CF2SO2)2, LiN(FSO2)2 (also recorded as Li(FSO2)2N in this specification) and LiN(CF3SO2)(C4F9SO2); perfluoroalkyl sulfonyl methyl salts such as LiC(CF3SO2)3; fluoroalkyl fluorophosphates (preferably perfluoroalkyl fluorophosphates) such as Li[PF5(CF2CF2CF3)], Li[PF4(CF2CF2CF3)2], Li[PF3(CF2CF2CF3)3], Li[PF5(CF2CF2CF2CF3)], Li[PF4(CF2CF2CF2CF3)2] and Li[PF3(CF2CF2CF2CF3)3].
[0214] (L-3) Oxalate borate: lithium bis(oxalato)borate and lithium difluorooxalatoborate.
[0215] In addition to the above, examples of lithium salts include LiF, LiCl, LiBr, LiI, Li2SO4, LiNO3, Li2CO3, CH3COOLi, LiAsF6, LiSbF6, LiAlCl4 and LiB(C6H5)4.
[0216] Among them, LiPF6, LiBF4, LiAsF6, LiSbF6, LiClO4, Li(R f11 SO2)、LiN(R f11 SO2)2, LiN(FSO2)2 or LiN(R f11 SO2)(R f12 SO2), more preferably LiPF6, LiBF4, LiN(R f11 SO2)2, LiN(FSO2)2 or LiN(R f11 SO2)(R f12 SO2). In these examples, R f11 and R f12 Each independently represents a perfluoroalkyl group and has a carbon number of preferably 1 to 6, more preferably 1 to 2. Furthermore, as the lithium salt, LiNO 3 and 1,1,2,2,3,3-hexafluoropropane-1,3-disulfonylimide lithium are also preferred.
[0217] (Elemental composition of solid electrolyte (II))
[0218] Regarding the solid electrolyte (II), the composition of the components is described based on the compound constituting the solid electrolyte (II). Next, the solid electrolyte (II) is described from the viewpoint of the preferred elemental composition. That is, in one embodiment of the electrode composition of the present invention, regarding the solid electrolyte (II), it is not considered as a specific invention item to have "lithium-containing oxide" and "lithium salt", but can be determined by the elemental composition, for example, as follows.
[0219] In the solid electrolyte (II) used in the present invention, when the molar amount of B in the solid electrolyte (II) is set to 4.00, the molar amount of Li is preferably 1.58 to 3.49 (preferably 1.58 to 3.00, more preferably 1.90 to 3.00, and further preferably 2.00 to 3.00). Furthermore, when the molar amount of B in the solid electrolyte (II) is set to 4.00, the molar amount of O is preferably 6.23 to 25.00 (preferably 6.50 to 23.00, more preferably 8.00 to 23.00, further preferably 10.00 to 23.00, and particularly preferably 10.00 to 18.00). Furthermore, when the molar amount of B in the solid electrolyte (II) is set to 4.00, the molar amounts of elements other than B, other than Li, and other than O are preferably 0.001 to 10.00 (preferably 0.001 to 6.00, and further preferably 0.01 to 5.00), respectively.
[0220] The content of each element is determined by conventional elemental analysis. As a method of elemental analysis, for example, Li and B are analyzed by ICP-OES (Inductively coupled plasma optical emission spectrometry), N and the like are analyzed by an inert gas fusion method, and for example, F and S are analyzed by combustion ion chromatography. For O, the analysis masses of elements other than O can be added and calculated as a difference from the total amount of powder. In addition, the method for calculating the content of each element is not limited to the above. Taking into account the structure of the compound used, the content of other elements can be estimated based on the analysis results of the content of one element.
[0221] Based on the content of each element calculated by elemental analysis, the molar amounts of Li, O, and other elements when the molar amount of B is set to 4.00 were calculated.
[0222] In a preferred embodiment of the solid electrolyte (II), in addition to Li, B and O, the solid electrolyte (II) also contains one or more elements (E) selected from the group consisting of elements of Group 4 of the periodic table, elements of Group 15 of the periodic table, elements of Group 16 of the periodic table, elements of Group 17 of the periodic table, Si, C, Sc and Y, and more preferably contains two or more elements.
[0223] Examples of the Group 4 elements of the periodic table include Ti, Zr, Hf and Rf. Examples of the Group 15 elements of the periodic table include N, P, As, Sb, Bi and Mc. Examples of the Group 16 elements of the periodic table include S, Se, Te, Po and Lv. Examples of the Group 17 elements of the periodic table include F, Cl, Br, I, At and Ts.
[0224] Among them, it is preferred that the element (E) contains one or more elements selected from F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf and N, and it is more preferred that the element (E) contains two or more elements selected from F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf and N.
[0225] The number of the elements (E) contained in the solid electrolyte (II) may be 3 or more, preferably 2 to 5, and more preferably 2 to 4.
[0226] A preferred embodiment of the solid electrolyte (II) preferably contains two or more elements (E) selected from F, S, N, P and C, more preferably contains two or more elements (E) selected from F, S, C and N, and further preferably contains three elements (E) of F, S and N.
[0227] In the solid electrolyte (II) containing one or more (preferably two or more) of the above-mentioned element (E), when the molar amount of B in the solid electrolyte (II) is set to 4.00 to express the molar amount of Li, the molar amount of Li is preferably 1.58 to 3.49. That is, when the molar content of B is set to 4.00, the relative value of the molar content of Li is preferably 1.58 to 3.49. Among them, when the molar amount of B in the solid electrolyte (II) is set to 4.00 to express the molar amount of Li, the molar amount of Li is preferably 1.58 to 3.00, more preferably 1.90 to 3.00, and further preferably 2.00 to 3.00.
[0228] In the solid electrolyte (II) containing one or more (preferably two or more) of the above-mentioned element (E), when the molar amount of B in the solid electrolyte (II) is set to 4.00 to represent the molar amount of O, the molar amount of O is preferably 6.23 to 25.00. That is, when the molar content of B is set to 4.00, the relative value of the molar content of O is preferably 6.23 to 25.00. Among them, when the molar amount of B in the solid electrolyte (II) is set to 4.00 to represent the molar amount of O, the molar amount of O is preferably 6.50 to 23.00, more preferably 8.00 to 23.00, more preferably 10.00 to 23.00, and particularly preferably 10.00 to 18.00.
[0229] In a solid electrolyte (II) comprising one or more (preferably two or more) of the above-mentioned element (E), when the molar amount of B in the solid electrolyte (II) is set to 4.00 to represent the molar amount of the element (E), the molar amount of each element (E) is preferably 0.001 to 10.00. That is, when the molar content of B is set to 4.00, the relative value of the molar content of each element (E) is preferably 0.001 to 10.00. Among them, when the molar amount of B in the solid electrolyte (II) is set to 4.00 to represent the molar amount of the element (E), the molar amount of each element (E) is preferably 0.001 to 6.00, and more preferably 0.01 to 5.00.
[0230] As one of the preferred aspects of the elemental composition of the solid electrolyte (II) containing one or more (preferably two or more) of the above-mentioned element (E), it can be mentioned that when Li, B, O, F, S and N are contained and the molar amount of B is 4.00, the molar amount of Li is 1.58 to 3.49 (preferably 1.58 to 3.00, more preferably 1.90 to 3.00, and further preferably 2.00 to 3.00), the molar amount of O is 6.23 to 25.00 (preferably The molar amount of F is 0.001-10.00 (preferably 0.01-10.00), the molar amount of S is 0.001-2.00 (preferably 0.01-2.00), and the molar amount of N is 0.001-1.00 (preferably 0.005-1.00) of the solid electrolyte.
[0231] The solid electrolyte (II) used in the present invention is the above-mentioned amorphous solid electrolyte. As a result, it is preferred that the solid electrolyte (II) exhibits the following characteristics in addition to the above-mentioned X-ray diffraction characteristics.
[0232] (Solid State 7 Li-NMR spectral characteristics)
[0233] Regarding the solid electrolyte (II), the solid electrolyte (II) was solidified at 20°C and 120°C. 7 The full width at half maximum ratio calculated from the spectrum obtained by Li-NMR measurement by the method described below is preferably 50% or less, more preferably 40% or less, and further preferably 35% or less. The lower limit is not particularly limited, but is often 10% or more.
[0234] The above-mentioned half-peak full width ratio is obtained by the following calculation: solid electrolyte (II) is solidified at 20°C and 120°C respectively. 7Li-NMR measurement, and after obtaining the half-maximum width (full width at half maximum 1) of the peak whose chemical shift appears in the range of -100 to +100 ppm in the spectrum obtained in the measurement at 20°C and the half-maximum width (full width at half maximum 2) of the peak whose chemical shift appears in the range of -100 to +100 ppm in the spectrum obtained in the measurement at 120°C, the percentage of the ratio of the half-maximum width 2 to the half-maximum width 1 is calculated {(full width at half maximum 2 / full width at half maximum 1) × 100}. The full width at half maximum (FWHM) of the peak refers to the width (ppm) at the 1 / 2 point (H / 2) of the height (H) of the peak.
[0235] Below, use Figure 4 The above characteristics are explained below. Figure 4 The solid electrolyte (II) is shown in Figure 2 at 20°C or 120°C. 7 An example of a spectrum obtained during Li-NMR measurement. Figure 4 The solid line spectrum shown on the lower side is the solid state spectrum at 20°C. 7 The spectrum obtained during Li-NMR measurement is Figure 4 The dotted spectrum shown on the upper side is a spectrum obtained by solid-state heating at 120°C. 7 Spectra obtained during Li-NMR measurement.
[0236] Generally speaking, in solid 7 In Li-NMR measurement, Li + In case of high mobility, the peak obtained is sharper. Figure 4 In the manner shown, when comparing the spectrum at 20°C with the spectrum at 120°C, the spectrum at 120°C becomes sharper. Figure 4 In the embodiment shown, it is shown that Li + The mobility of the solid electrolyte (II) is increased. It is believed that this solid electrolyte (II) becomes susceptible to plastic deformation due to the defective structure as described above, and Li + Excellent jumping performance.
[0237] For reference, regarding ordinary lithium tetraborate crystals, solid-state 7 During Li-NMR measurement, Figure 5 The spectrum measured at 20°C is shown by the solid line at the bottom of Figure 5 The spectra measured at 120° C. indicated by the dotted line shown above tend to have substantially the same shape. That is, in the lithium tetraborate crystal, there are no Li defects or the like, and as a result, the elastic modulus is high and plastic deformation is not easily caused.
[0238] The above solid 7 Li-NMR measurement conditions are as follows.
[0239] The measurement was performed using a 4 mm HX CP-MAS probe by a single pulse method with a 90° pulse width of 3.2 μs, an observation frequency of 155.546 MHz, an observation width of 1397.6 ppm, a repetition time of 15 seconds, a cumulative integration of 1 time, and a MAS rotation speed of 0 Hz.
[0240] Furthermore, the solid electrolyte (II) used in the present invention is preferably as follows: 7 When the first peak appearing in the range of -100 to +100 ppm in the spectrum obtained during Li-NMR measurement is subjected to waveform separation, there is a second peak having a chemical shift in the range of -3 to 3 ppm and a half-maximum width of 5 ppm or less, and the ratio of the area intensity of the second peak to the area intensity of the first peak is 0.5% or more. The ratio of the above-mentioned area intensity is more preferably 2% or more, further preferably 5% or more, particularly preferably 10% or more, and most preferably 15% or more. In the embodiment of the present invention wherein the solid electrolyte (II) contains water, the solid electrolyte (II) 7 The Li-NMR spectrum characteristics tend to be as described above. The upper limit of the ratio of the area intensity is not particularly limited, but is often 50% or less.
[0241] Below, use Figure 6 and Figure 7 The above characteristics are described.
[0242] exist Figure 6 The solid electrolyte (II) is shown in FIG. 7 An example of a spectrum obtained during Li-NMR measurement. Figure 6 As shown, a peak (corresponding to the first peak) is observed in the solid electrolyte (II) in the range of -100 to +100 ppm, and in the first peak, a small peak surrounded by a dotted line is observed near the chemical shift of 0 ppm. + When the mobility is high, a sharp peak can be observed, thus producing its influence.
[0243] Then, in Figure 7 , a diagram showing the separation of the first peak waveform is shown. Figure 7 As shown, the first peak is separated into a small peak (corresponding to the second peak) represented by a solid line and a large peak represented by a dotted line. The second peak is a peak with a chemical shift in the range of -3 to 3 ppm and a full width at half maximum of less than 5 ppm.
[0244] The solid electrolyte (II) is preferably composed of Figure 7 The solid line represents the area intensity of the second peak relative to that of Figure 6 The ratio of the area intensity of the first peak (the peak before the waveform separation) {(area intensity of the second peak / area intensity of the first peak)×100(%)} is within the above range.
[0245] As a method of waveform separation, a method using known software can be mentioned. As software, for example, Igor Pro, a graphics processing software of WaveMetrics, Inc. can be mentioned.
[0246] (Raman spectroscopy characteristics)
[0247] Regarding solid electrolyte (II), in the Raman spectrum of solid electrolyte (II), 600-850 cm -1 In the wave number region, the coefficient of determination obtained by linear regression analysis by the least square method is preferably 0.9400 or more, more preferably 0.9600 or more, and also preferably 0.9800 or more. The upper limit is not particularly limited, but is usually 1.0000 or less.
[0248] refer to Figure 8 , the above Raman spectral characteristics are explained.
[0249] First, a Raman spectrum of the solid electrolyte (II) is obtained. As a method for measuring Raman spectra, Raman imaging is implemented. Raman imaging refers to microscopic spectroscopy combined with microscopy in Raman spectroscopy. Specifically, it is a method of detecting measurement light containing Raman scattered light by scanning excitation light on a sample, and visualizing the distribution of components based on the intensity of the measurement light.
[0250] The measurement conditions of Raman imaging are as follows: 27°C and in the atmosphere, excitation light of 532nm, objective lens of 100 times, point scanning in mapping mode, 1μm step length, exposure time of 1 second per point, accumulation and integration times of 1 time, and measurement range of 70μm×50μm. However, the measurement range may become narrower depending on the film thickness of the sample.
[0251] Furthermore, the Raman spectrum data is subjected to principal component analysis (PCA) processing to remove noise. Specifically, in the principal component analysis processing, the spectrum is reorganized using components having an autocorrelation coefficient of 0.6 or more.
[0252] exist Figure 8 An example of the Raman spectrum of the solid electrolyte (II) is shown in FIG. Figure 8 In the graph shown, the vertical axis represents the Raman intensity and the horizontal axis represents the Raman shift. Figure 8 The Raman spectrum shown is 600-850 cm -1The coefficient of determination (R 2 ). That is, in Figure 8 The Raman spectrum of 600-850 cm -1 In the wave number region, the regression line is obtained by the least square method ( Figure 8 The bold line in the figure is used to calculate the coefficient of determination R of the regression line. 2 In addition, the coefficient of determination takes a value between 0 (no linear correlation) and 1 (complete linear correlation of the measured values) depending on the linear correlation of the measured values.
[0253] In solid electrolytes (II), such as Figure 8 As shown, at 600-850cm -1 In the wavenumber region, almost no peak is observed, and as a result, a high determination coefficient is shown.
[0254] In addition, the above determination coefficient R 2 It is equivalent to the square of the correlation coefficient (Pearson product-moment correlation coefficient). More specifically, in this specification, the coefficient of determination R 2 The calculation is performed by the following formula: wherein x1 and y1 represent the wave number in the Raman spectrum and the Raman intensity corresponding to the wave number, x2 represents the (arithmetic) average of the wave number, and y2 represents the (arithmetic) average of the Raman intensity.
[0255] [Formula 8]
[0256]
[0257] On the other hand, for reference, Fig. 9 The Raman spectrum of a typical lithium tetraborate crystal is shown in FIG. Fig. 9 As shown, in the case of a conventional lithium tetraborate crystal, the wavelengths of 716 to 726 cm-1 are derived from its structure. -1 and 771~785cm -1 In the wave number region of 600-850 cm -1 In the wave number region, when the coefficient of determination was calculated by linear regression analysis using the least squares method, the coefficient of determination was less than 0.9400.
[0258] That is, when the above determination coefficient is 0.9400 or more, it means that the solid electrolyte (II) contains almost no crystal structure. Therefore, as a result, it is considered that the solid electrolyte (II) has the characteristics of being easy to plastically deform and Li + Excellent jumping properties.
[0259] (Infrared absorption spectrum characteristics)
[0260] In the infrared absorption spectrum of solid electrolyte (II), the -1 The maximum absorption intensity in the wave number region is relatively large compared to that in the region of 800 to 1600 cm -1 The ratio of the maximum absorption intensity in the wave number region (between 3000 and 3500 cm -1 The maximum absorption intensity in the wave number region of 800 to 1600 cm -1 The maximum absorption intensity in the wave number region of the wavelength region is preferably 1 / 5 or more (0.2 or more). Among them, the above ratio is preferably 3 / 10 or more, more preferably 2 / 5 or more. The upper limit is not particularly limited, but is preferably 1 or less.
[0261] In the infrared absorption spectrum, the range of 3000 to 3500 cm -1 The OH stretching vibration mode is observed in the wave number region of 800-1600 cm -1 The BO stretching vibration mode is observed in the wave number region of . It can be seen that in the solid electrolyte (II), the absorption intensity derived from the OH stretching vibration mode is strong, which shows that a large number of OH groups and / or a large amount of water are contained. In this solid electrolyte (II), lithium ions become easy to move, and as a result, the ion conductivity tends to be improved.
[0262] In addition, at 800-1600cm -1 In the wave number region, vibration modes originating from lithium salts can also be observed.
[0263] The infrared absorption spectrum measurement conditions can be set as follows.
[0264] Objective lens: 32x Cassegrain (NA0.65), Detector: MCT-A, Measuring range: 650~4000cm -1 , Resolution: 4cm -1 , Sample cell: Use diamond cell for measurement.
[0265] The infrared absorption spectrum obtained was corrected to remove signals from water and CO 2 in the atmosphere, and the background was offset corrected so that the absorption intensity became 0. After vacuum drying at 40° C. for 2 hours, the spectrum was measured in the atmosphere.
[0266] The ion conductivity (27°C) of the solid electrolyte (II) is not particularly limited, but is preferably 1.0×10 -5 S / cm or more, more preferably 1.0×10 -4 S / cm or more, more preferably 1.0×10 -3 S / cm or more, particularly preferably 3.0×10 -3S / cm or more. The upper limit is not particularly limited, but is often 1.0×10 -2 S / cm or less.
[0267] Furthermore, the solid electrolyte (II) also preferably exhibits the following characteristics or properties.
[0268] (Mass reduction rate)
[0269] The mass reduction rate of the solid electrolyte (II) when heated to 800°C is preferably 20 to 40% by mass, more preferably 25 to 35% by mass. The mass reduction caused by the above heating is believed to be due to the removal of water contained in the solid electrolyte (II). The solid electrolyte (II) can further improve the conductivity of lithium ions by containing such water.
[0270] In the above-mentioned heating treatment, heating is performed at a temperature increase rate of 20°C / second within a range of 25°C to 800°C. When measuring the mass reduction, a known thermogravimetric differential thermal analysis (TG-DTA) device can be used. The above-mentioned mass reduction rate is calculated as follows:
[0271] {(mass at 25°C - mass at 800°C) / mass at 25°C}×100.
[0272] When measuring the mass reduction rate, the solid electrolyte (II) was previously vacuum dried at 40° C. for 2 hours. The mass reduction rate was measured in the atmosphere.
[0273] Furthermore, the electrode composition of the present invention may include other solid electrolytes in addition to the solid electrolyte (I). Other solid electrolytes refer to solid electrolytes that enable ions to move inside them. As solid electrolytes, inorganic solid electrolytes are preferred. As other solid electrolytes, oxide-based solid electrolytes, halide-based solid electrolytes, and hydride-based solid electrolytes other than the solid electrolyte (I) can be cited, preferably oxide-based solid electrolytes.
[0274] <Active substances>
[0275] As the active material constituting the electrode composition of the present invention, positive electrode active materials and negative electrode active materials that can be used for ordinary all-solid-state secondary batteries can be used without particular limitation.
[0276] The shape of the active material is a particle. The median diameter M of the active material is not particularly limited as long as it is the above-mentioned M / N, and is, for example, preferably 0.1 to 20 μm, more preferably 0.3 to 20 μm, and particularly preferably 0.5 to 15 μm. The median diameter M of the active material can be measured using a laser diffraction / scattering particle size distribution measuring device.
[0277] The method for controlling the median diameter M of the active material is not particularly limited, and can be performed by a common method.
[0278] The control of the median diameter of the active material can be carried out using a pulverizer or a classifier. For example, a mortar, a ball mill, a sand mill, a vibrating ball mill, a satellite ball mill, a planetary ball mill, a rotary airflow type jet mill or a sieve can be preferably used. When pulverizing, wet pulverization can also be carried out in the presence of an organic solvent such as water or methanol. In order to obtain a desired particle size, it is preferably classified. As a classification method, it is not particularly limited, and a sieve, a wind classifier, etc. can be used as desired. Regarding classification, both dry and wet methods can be used. Preferably, the particle size is refined by mechanical grinding in the same manner as the solid electrolyte (I), and controlled by screening.
[0279] Hereinafter, preferred embodiments of the positive electrode active material and the negative electrode active material will be described.
[0280] In the following description, the case of using a solid electrolyte (II) (in the form of an all-solid-state lithium-ion secondary battery) is used as an example, but even when using a solid electrolyte (I) containing an alkali metal or alkaline earth metal other than lithium, it can be appropriately implemented by referring to this description.
[0281] Hereinafter, preferred embodiments of the positive electrode active material will be described.
[0282] (Positive electrode active material)
[0283] The positive electrode active material is preferably a positive electrode active material that can reversibly insert and / or release lithium ions. The positive electrode active material is not particularly limited, preferably a transition metal oxide, more preferably a transition metal oxide containing a transition metal element Ma (one or more elements selected from Co, Ni, Fe, Mn, Cu and V). In addition, the element Mb (metal elements of the 1st (Ia) group of the periodic table other than lithium, elements of the 2nd (IIa) group, Al, Ga, In, Ge, Sn, Pb, Sb, Bi, Si, P and B, etc.) can be mixed in the transition metal oxide. As the mixing amount of the element Mb, it is preferably 0 to 30 mol% relative to the amount of the transition metal element Ma (100 mol%). More preferably, the material synthesized by mixing in a manner such that the molar ratio of Li / Ma is 0.3 to 2.2.
[0284] Specific examples of transition metal oxides include (MA) transition metal oxides having a layered rock salt structure, (MB) transition metal oxides having a spinel structure, (MC) transition metal phosphate compounds containing lithium, (MD) transition metal halophosphate compounds containing lithium, and (ME) transition metal silicate compounds containing lithium. Among them, (MA) transition metal oxides having a layered rock salt structure are preferred, and LiCoO2 or LiNi2O3 are more preferred. 1 / 3 Co 1 / 3 Mn 1 / 3 O2.
[0285] Examples of the transition metal oxide (MA) having a layered rock salt structure include LiCoO2 (lithium cobalt oxide [LCO]), LiNiO2 (lithium nickel oxide [LNO]), LiNi 0.85 Co 0.10 Al 0.05 O2 (nickel cobalt aluminum oxide [NCA]), LiNi 1 / 3 Mn 1 / 3 Co 1 / 3O2 (lithium nickel manganese cobalt oxide [NMC]), LiNi 0.5 Mn 0.5 O2 (lithium manganese nickel oxide) and Li2MnO3-LiNiMnCoO2.
[0286] Examples of the transition metal oxide (MB) having a spinel structure include LiMn2O4 (LMO), LiNi 0.5 Mn 1.5 O4([LNMO]), LiCoMnO4, Li2FeMn3O8, Li2CuMn3O8, Li2CrMn3O8 and Li2NiMn3O8.
[0287] As (MC) transition metal phosphate compounds containing lithium, for example, there can be mentioned olivine-type iron phosphate salts such as LiFePO4([LFP]) and Li3Fe2(PO4)3, pyrophosphate iron salts such as LiFeP2O7, olivine-type manganese phosphate salts such as LiMnPO4[(LMP)], olivine-type nickel phosphate salts such as LiNiPO4[(LNP)], olivine-type cobalt phosphate salts such as LiCoPO4[(LCP)], olivine-type cobalt pyrophosphate salts such as Li2CoP2O7, and monoclinic NASICON-type vanadium phosphate salts such as Li3V2(PO4)3(lithium vanadium phosphate).
[0288] Examples of the lithium-containing transition metal halophosphate compound (MD) include iron fluorophosphates such as Li2FePO4F, manganese fluorophosphates such as Li2MnPO4F, and cobalt fluorophosphates such as Li2CoPO4F.
[0289] Examples of the (ME) lithium-containing transition metal silicate compound include Li 2 FeSiO 4 , Li 2 MnSiO 4 , and Li 2 CoSiO 4 .
[0290] The positive electrode active material obtained by the calcination method can be used after being washed with water, an acidic aqueous solution, an alkaline aqueous solution, or an organic solvent.
[0291] The positive electrode active material may be surface-coated with a surface coating agent, sulfur or phosphorus, which will be described later, in the same manner as the negative electrode active material, which will be described later, or with active light.
[0292] The positive electrode active material may be used alone or in combination of two or more.
[0293] Among these, LiCoO2 (LCO), LiMn2O4 (LMO) and LiNi 1 / 3 Mn 1 / 3 Co 1 / 3O2(NMC).
[0294] Hereinafter, preferred embodiments of the negative electrode active material will be described.
[0295] (Negative electrode active material)
[0296] The negative electrode active material is preferably a negative electrode active material that can reversibly insert and release lithium ions. The negative electrode active material is not particularly limited, and examples thereof include carbonaceous materials, oxides of metal elements or semi-metal elements, lithium monomers, lithium alloys, and negative electrode active materials that can form alloys with lithium.
[0297] The carbonaceous material used as the negative electrode active material refers to a material substantially composed of carbon, for example, carbonaceous materials made of various synthetic resins such as calcined petroleum pitch, carbon black such as acetylene black (AB), graphite (natural graphite and artificial graphite such as vapor-grown graphite), and PAN (polyacrylonitrile) resin or furfuryl alcohol resin.
[0298] In addition, various carbon fibers such as PAN-based carbon fibers, cellulose-based carbon fibers, pitch-based carbon fibers, vapor-grown carbon fibers, dehydrated PVA (polyvinyl alcohol)-based carbon fibers, lignin carbon fibers, glassy carbon fibers, and activated carbon fibers, as well as intermediate phase microspheres, graphite whiskers, and flat graphite can also be cited.
[0299] These carbonaceous materials can be further divided into hardly graphitizable carbonaceous materials (also called hard carbon) and graphite-based carbonaceous materials according to the degree of graphitization.
[0300] Furthermore, the carbonaceous material preferably has the interplanar spacing, density or crystallite size described in Japanese Patent Laid-Open No. 62-022066, Japanese Patent Laid-Open No. 2-006856 and Japanese Patent Laid-Open No. 3-045473. The carbonaceous material need not be a single material, and a mixture of natural graphite and artificial graphite described in Japanese Patent Laid-Open No. 5-090844 and graphite with a coating layer described in Japanese Patent Laid-Open No. 6-004516 can also be used.
[0301] As the carbonaceous material, hard carbon or graphite is preferred, and graphite is more preferred.
[0302] The oxide of the metal element or semi-metal element used as the negative electrode active material is not particularly limited as long as it is an oxide that can occlude and release lithium, and examples thereof include oxides of metal elements such as Fe3O4 (metal oxides), composite oxides of metal elements, composite oxides of metal elements and semi-metal elements, and oxides of semi-metal elements (semi-metal oxides). In addition, composite oxides of metal elements and composite oxides of metal elements and semi-metal elements are collectively referred to as metal composite oxides.
[0303] As these oxides, amorphous oxides are preferred, and chalcogenides which are reaction products of metal elements and elements of Group 16 of the periodic table are also preferred.
[0304] In the present invention, semi-metallic elements refer to elements showing properties between metal elements and non-metallic elements, and generally include six elements of boron, silicon, germanium, arsenic, antimony and tellurium, and also include three elements of selenium, polonium and astatine.
[0305] Furthermore, the "amorphous" of the amorphous oxide means that it has a broad scattering band having a vertex in the region of 2θ values of 20 to 40°, and may also have crystalline diffraction lines, according to the X-ray diffraction method using CuKα rays. It is preferred that the strongest intensity of the crystalline diffraction lines seen in the region of 2θ values of 40 to 70° is 100 times or less, more preferably 5 times or less, and further preferably is a diffraction line having no crystalline diffraction line intensity at the vertex of the broad scattering band seen in the region of 2θ values of 20 to 40°.
[0306] Among the compound group consisting of the above-mentioned amorphous oxides and chalcogenides, amorphous oxides of semimetallic elements or the above-mentioned chalcogenides are more preferred, and (complex) oxides or chalcogenides consisting of a single element or a combination of two or more elements selected from Groups 13 (IIIB) to 15 (VB) of the periodic table (for example, Al, Ga, Si, Sn, Ge, Pb, Sb and Bi) are further preferred.
[0307] As amorphous oxides and chalcogenides, preferred are Ga2O3, GeO, PbO, PbO2, Pb2O3, Pb2O4, Pb3O4, Sb2O3, Sb2O4, Sb2O8Bi2O3, Sb2O8Si2O3, Sb2O5, Bi2O3, Bi2O4, GeS, PbS, PbS2, Sb2S3 or Sb2S5.
[0308] As the negative electrode active material that can be used together with the amorphous oxide negative electrode active material centered on Sn, Si or Ge, carbonaceous materials that can occlude and / or release lithium ions or lithium metal, lithium monomers, lithium alloys, or negative electrode active materials that can alloy with lithium are preferred.
[0309] From the viewpoint of high current density charge and discharge characteristics, the oxide of a metal element or a semi-metal element (particularly a metal (complex) oxide) and the above-mentioned chalcogenide preferably contain at least one of titanium and lithium as a constituent component.
[0310] Examples of the metal composite oxide containing lithium (lithium composite metal oxide) include composite oxides of lithium oxide and the above-mentioned metal oxides, the above-mentioned metal composite oxides or the above-mentioned chalcogenides. More specifically, Li2SnO2 is included.
[0311] The negative electrode active material (e.g., metal oxide) also preferably contains titanium (titanium oxide). Specifically, since the volume change when absorbing and releasing lithium ions is small, the rapid charge and discharge characteristics are excellent. From the perspective of being able to increase the life of the all-solid-state lithium ion secondary battery that suppresses electrode degradation, Li4Ti5O is preferred. 12 (lithium titanate [LTO]).
[0312] The lithium alloy used as the negative electrode active material is not particularly limited as long as it is an alloy commonly used as a negative electrode active material for all-solid-state lithium ion secondary batteries, and examples thereof include lithium aluminum alloys.
[0313] The negative electrode active material capable of forming an alloy with lithium is not particularly limited as long as it is a material commonly used as a negative electrode active material for an all-solid-state lithium-ion secondary battery. As the above-mentioned negative electrode active material, negative electrode active materials (alloys) containing silicon or tin elements and metals such as Al and In can be cited, preferably negative electrode active materials containing silicon elements (active materials containing silicon elements) that can achieve higher battery capacity, and more preferably active materials containing silicon elements with a silicon content of more than 50 mol% of all constituent elements.
[0314] Generally speaking, a negative electrode containing these negative electrode active materials (for example, an Si negative electrode containing an active material containing silicon element, an Sn negative electrode containing an active material containing tin element) can occlude more Li ions compared with a carbon negative electrode (such as graphite and acetylene black). That is, the occluding amount of Li ions per unit mass increases. Therefore, the battery capacity can be increased. As a result, it has the advantage of being able to extend the battery driving time.
[0315] As the active material containing silicon element, for example, silicon materials such as Si and SiOx (0 < x ≤ 1) can be cited. Further, silicon-containing alloys containing titanium, vanadium, chromium, manganese, nickel, copper or lanthanum (for example, LaSi2, VSi2, La-Si, Gd-Si and Ni-Si) or organized active materials (for example, LaSi2 / Si) can be cited. In addition, active materials containing silicon element and tin element such as SnSiO3 and SnSiS3 can be cited. In addition, regarding SiOx, it can be used as a negative electrode active material (semi-metal oxide) itself, and Si is generated by the operation of an all-solid-state lithium ion secondary battery, so it can be used as a negative electrode active material (its precursor material) capable of alloying with lithium.
[0316] As the negative electrode active material having tin element, for example, those containing Sn, SnO, SnO2, SnS, SnS2 and the above-mentioned active materials containing silicon element and tin element can be cited.
[0317] From the viewpoint of battery capacity, as the negative electrode active material, a negative electrode active material capable of alloying with lithium is preferred, more preferably the above-mentioned silicon materials or silicon-containing alloys (alloys containing silicon element), and still more preferably silicon (Si) or silicon-containing alloys.
[0318] As the negative electrode active material, it is also preferable to use a titanium niobium composite oxide. The theoretical volume capacity density of the titanium niobium composite oxide is high, and it can be expected to have a long life and also be capable of rapid charging. As the titanium niobium composite oxide, for example, TiNb2O7 ([TNO]) can be cited.
[0319] The negative electrode active material can be used alone in one kind, or two or more kinds can be used simultaneously.
[0320] The surface of the negative electrode active material can be surface-coated with an oxide such as other metal oxides or a carbon-based material. These surface coating layers can function as an interface resistance stabilizing layer.
[0321] As the surface coating agent, metal oxides containing Ti, Nb, Ta, W, Zr, Al, Si or Li can be cited. Specifically, spinel titanate, tantalum-based oxides, niobium-based oxides and lithium niobate-based compounds can be cited. For example, Li4Ti5O can be cited. 12, Li2Ti2O5, LiTaO3, LiNbO3, LiAlO2, Li2ZrO3, Li2WO4, Li2TiO3, Li2B4O7, Li3PO4, Li2MoO4, Li3BO3, LiBO2, Li2CO3, Li2SiO3, SiO2, TiO2, ZrO2, Al2O3, B2O3 and Li3AlF6. In addition, carbon-based materials such as C, SiC, and SiOC (carbon-doped silicon oxide) can also be used as surface coating materials.
[0322] Furthermore, the surface of the negative electrode active material may be surface-treated with sulfur or phosphorus.
[0323] Furthermore, the surface of the particles of the negative electrode active material may be subjected to a surface treatment using active light or active gas (for example, plasma) before or after the surface is coated.
[0324] Among these, Li4Ti5O is preferred as the negative electrode active material. 12 (LTO).
[0325] <Other ingredients>
[0326] The electrode composition of the present invention may contain components (other components) other than the solid electrolyte and the active material. For example, a conductive auxiliary agent may be contained.
[0327] As the conductive auxiliary agent, a substance generally known as a conductive auxiliary agent can be used. As the conductive auxiliary agent, for example, graphites such as natural graphite and artificial graphite, carbon blacks such as acetylene black, Ketjen black and furnace black, amorphous carbon such as needle coke, fibrous carbon such as vapor-grown carbon fiber and carbon nanotubes, and carbonaceous materials such as graphene and fullerene can be cited as electron conductive materials. In addition, conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene and polyphenylene derivatives can be used.
[0328] In addition to the above-mentioned conductive additives, a common conductive additive containing no carbon atoms, such as metal powder or metal fiber, can be used.
[0329] A conductive aid is an aid that does not insert or release Li during battery charge and discharge and does not function as an active material. Therefore, among conductive aids, substances that function as active materials in the active material layer during battery charge and discharge are also classified as active materials rather than conductive aids. Whether or not a conductive aid functions as an active material during battery charge and discharge is not unique, but is determined by the combination with the active material.
[0330] The content of the conductive aid in the solid content of the electrode composition for the positive electrode active material layer is not particularly limited, but is, for example, preferably 0 to 10% by mass, and more preferably 1 to 8% by mass.
[0331] The content of the conductive aid in the solid content of the electrode composition for the negative electrode active material layer is not particularly limited, but is, for example, preferably 0 to 10% by mass, and more preferably 1 to 8% by mass.
[0332] As other components, a binder may also be mentioned.
[0333] As a binder, a binder composed of an organic polymer can be included. The organic polymer constituting the binder can be in a particle form or a non-particle form. By including a binder, cracks can be more reliably prevented from occurring in the active material layer.
[0334] As the organic polymer constituting the binder, a common organic polymer used in the electrode composition can be used. The organic polymer can be water-soluble or water-insoluble. As the water-soluble polymer, cellulose polymers such as sodium polyacrylate (PAA-Na), water-soluble alginic acid derivatives, carboxymethyl cellulose, polyacrylamide, etc. can be cited.
[0335] The binder contained in the electrode composition of the present invention may contain a copolymer latex. The type of copolymer latex is not particularly limited, and examples thereof include conjugated diene copolymers such as styrene-butadiene copolymers, acrylonitrile-butadiene copolymers, methyl methacrylate-butadiene copolymers, vinyl pyridine-butadiene copolymers, acrylic polymers, vinyl acetate polymers, ethylene-vinyl acetate copolymers, chloroprene polymers, natural rubber and other aqueous dispersions, among which conjugated diene copolymers and acrylic copolymers are preferred. Among them, one or more kinds can be used. The median diameter of the copolymer latex based on the photon correlation method is preferably 10 to 500 nm, more preferably 50 to 300 nm, and further preferably 100 to 200 nm.
[0336] As other components, the above-mentioned lithium salt may be contained separately without being a component of the solid electrolyte (I).
[0337] As other components, a liquid medium can also be mentioned.
[0338] The electrode composition of the present invention preferably contains water, but may also contain a liquid medium other than water. As the liquid medium other than water, for example, an organic solvent that does not phase separate when mixed with water (hereinafter referred to as a water-soluble organic solvent) can be cited, specifically, N-methylpyrrolidone, methanol, ethanol, acetone, tetrahydrofuran, etc. can be cited.
[0339] When the electrode composition of the present invention contains a liquid medium, the content of the solid component (solid electrolyte (I), active material and other components other than the liquid medium) in the electrode composition of the present invention can be adjusted to, for example, 10 to 90% by mass, preferably 20 to 80% by mass, and more preferably 30 to 70% by mass. The concentration of the solid component in the electrode composition of the present invention can also be 55 to 90% by mass, preferably 60 to 90% by mass, more preferably 70 to 90% by mass, and further preferably 75 to 90% by mass.
[0340] When the electrode composition of the present invention is an electrode composition for a positive electrode active material layer, the content of the positive electrode active material in the solid component of the electrode composition is not particularly limited, and is preferably 10 to 97% by mass, more preferably 30 to 95% by mass, further preferably 40 to 93% by mass, and particularly preferably 50 to 90% by mass.
[0341] When the electrode composition of the present invention is an electrode composition for a positive electrode active material layer, the content of the solid electrolyte (I) in the solid component of the electrode composition is not particularly limited, and the total content with the positive electrode active material is preferably 50 to 99.9% by mass, more preferably 70 to 99.5% by mass, and further preferably 90 to 99% by mass.
[0342] When the electrode composition of the present invention is an electrode composition for a negative electrode active material layer, the content of the negative electrode active material in the solid component of the electrode composition is not particularly limited, and is preferably 10 to 90 mass %, more preferably 20 to 85 mass %, further preferably 30 to 80 mass %, and particularly preferably 40 to 75 mass %.
[0343] When the electrode composition of the present invention is an electrode composition for a negative electrode active material layer, the content of the solid electrolyte (I) in the solid component of the electrode composition is not particularly limited, and the total content with the negative electrode active material is preferably 50 to 99.9% by mass, more preferably 70 to 99.5% by mass, and further preferably 90 to 99% by mass.
[0344] The contents of the solid components are substantially the same in the active material layer formed using the electrode composition and in the secondary battery using the active material layer.
[0345] The electrode composition of the present invention can be obtained by mixing the solid electrolyte (I) and the active material, and optionally further mixing the above-mentioned other components.
[0346] [Electrode sheet for all-solid-state secondary batteries]
[0347] The electrode sheet for an all-solid-state secondary battery of the present invention (hereinafter also referred to as the electrode sheet of the present invention) has an active material layer formed using the electrode composition of the present invention. That is, the electrode sheet of the present invention contains the above-mentioned solid electrolyte (I) and an active material in the active material layer.
[0348] The active material layer of the electrode sheet of the present invention is preferably formed by pressurizing a layer formed using the electrode composition of the present invention.
[0349] The electrode sheet of the present invention has an active material layer showing excellent flexibility. That is, since the solid electrolyte (I) is an oxide-based solid electrolyte that can easily undergo plastic deformation under pressure, it is believed that by the plastic deformation of the solid electrolyte (I), the solid electrolyte (I) is made to fit each other and the active material and the like and show higher flexibility. In addition, the solid electrolyte (I) itself is soft and undergoes plastic deformation, and its function is similar to that of an adhesive, which helps to improve the cohesiveness between particles, so that the layer can also be formed without using an adhesive such as an organic polymer.
[0350] The electrode sheet of a secondary battery generally consists of a current collector and an active material layer. However, the electrode sheet of the present invention may be a single active material layer when the active material layer (for example, a layer formed using the electrode composition of the present invention) also functions as a current collector.
[0351] The active material layer included in the electrode sheet of the present invention may be a positive electrode active material layer containing a positive electrode active material, or may be a negative electrode active material layer containing a negative electrode active material.
[0352] The thickness of the active material layer constituting the electrode sheet of the present invention is not particularly limited, and can be, for example, 10 to 200 μm, preferably 15 to 150 μm.
[0353] The thickness of the current collector constituting the electrode sheet of the present invention is not particularly limited, and can be, for example, 5 to 50 μm, preferably 8 to 30 μm.
[0354] The current collector constituting the electrode sheet of the present invention is an electron carrier and is usually in a sheet shape. The current collector can be appropriately selected according to the active material.
[0355] As the constituent material of the positive electrode collector, aluminum (Al), aluminum alloy (Al alloy), stainless steel, nickel and titanium can be cited, preferably aluminum or aluminum alloy. In addition, as the positive electrode collector, a positive electrode collector (forming a thin film) treated with carbon, nickel, titanium or silver on the surface of aluminum or stainless steel can also be cited.
[0356] As the constituent material of the negative electrode collector, aluminum, copper (Cu), copper alloy, stainless steel, nickel and titanium can be enumerated, preferably aluminum, copper, copper alloy or stainless steel. In addition, as the negative electrode collector, a negative electrode collector treated with carbon, nickel, titanium or silver on the surface of aluminum, copper, copper alloy or stainless steel can also be enumerated.
[0357] The electrode sheet of the present invention may have, for example, a protective layer such as a release sheet or a coating layer as other layers.
[0358] The electrode sheet of the present invention can be preferably used as a material constituting a negative electrode active material layer or a positive electrode active material layer of a secondary battery, or as a laminate of a negative electrode collector and a negative electrode active material layer (negative electrode layer) or a laminate of a positive electrode collector and a positive electrode active material layer (positive electrode layer).
[0359] [All-solid-state secondary battery]
[0360] The all-solid-state secondary battery of the present invention (hereinafter also referred to as "the secondary battery of the present invention") is configured in sequence with a positive electrode active material layer, a solid electrolyte layer and a negative electrode active material layer, wherein at least one of the positive electrode active material layer and the negative electrode active material layer has an active material layer formed using the electrode composition of the present invention. That is, at least one of the positive electrode active material layer and the negative electrode active material layer is an active material layer comprising an amorphous solid electrolyte and an active material (a positive electrode active material in the case of the positive electrode active material layer, and a negative electrode active material in the case of the negative electrode active material layer), and the amorphous solid electrolyte comprises: a metal oxide containing at least one of an alkali metal element and an alkaline earth metal element and an oxygen element, at least one metal salt of an alkali metal salt and an alkaline earth metal salt, and water. In addition, the ratio of the median diameter M of the active material in the active material layer to the median diameter N of the solid electrolyte is controlled to be 0.05≤M / N<1.2.
[0361] As described above, in the secondary battery of the present invention, at least one of the positive electrode active material layer and the negative electrode active material layer can be a layer formed using the electrode composition of the present invention, and the remaining positive electrode active material layer and the negative electrode active material layer can be the same as the positive electrode active material layer and the negative electrode active material layer in a conventional all-solid-state secondary battery. It is also possible to set both the positive electrode active material layer and the negative electrode active material layer as layers formed using the electrode composition of the present invention.
[0362] The thickness of the positive electrode active material layer and the negative electrode active material layer constituting the secondary battery of the present invention is the same as the thickness of the active material layer in the electrode sheet of the present invention, and the preferred range is also the same.
[0363] The solid electrolyte layer constituting the secondary battery of the present invention is not particularly limited, and can be set to the same structure as the solid electrolyte layer in a conventional all-solid-state secondary battery. From the viewpoint of improving ion conductivity and flexibility, as a solid electrolyte, it is preferred to use the above-mentioned solid electrolyte (I), and it is more preferred to use a solid electrolyte (II). In addition to the solid electrolyte (I), the solid electrolyte layer may also include the above-mentioned "adhesive", the above-mentioned "other solid electrolytes", etc.
[0364] The thickness of the solid electrolyte layer constituting the secondary battery of the present invention is not particularly limited, and can be, for example, 5 to 1000 μm, preferably 10 to 100 μm.
[0365] The secondary battery of the present invention is preferably a so-called all-solid-state lithium ion secondary battery. It is preferred to use a solid electrolyte (II) in each of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer.
[0366] The materials and components used in the secondary battery of the present invention are not particularly limited except that the secondary battery of the present invention has the above-mentioned specific positive electrode active material layer, solid electrolyte layer and negative electrode active material layer. The materials and components used in conventional all-solid-state secondary batteries can be used.
[0367] [Method for producing electrode sheet for all-solid-state secondary battery]
[0368] The manufacturing method of the electrode sheet for secondary battery of the present invention uses the electrode composition of the present invention to form an active material layer, and in addition, it can be carried out with reference to the manufacturing method of the electrode sheet for all-solid-state secondary battery. That is, the manufacturing method of the electrode sheet of the present invention includes the step of using the electrode composition of the present invention to form an active material layer.
[0369] Specifically, the active material layer can be formed by applying the electrode composition (electrode slurry) of the present invention to form a layer.
[0370] When a current collector is used, the active material layer can be formed by coating the electrode composition of the present invention on the current collector to form a coating layer.
[0371] When the electrode composition contains a dispersion medium (liquid medium), the coating layer can be dried to form an active material layer. The drying method is not particularly limited, and for example, a dryer can be used, or vacuum drying, freeze vacuum drying, or heat treatment can be performed.
[0372] Furthermore, the active material layer can also be formed by simply press-molding the electrode composition of the present invention and forming it into a layer. For example, the active material layer can be formed by filling the powder of the electrode composition of the present invention into a predetermined mold and press-molding it.
[0373] The active material layer is preferably subjected to a pressure treatment. The conditions for the pressure treatment are not particularly limited, but the pressure treatment is preferably performed at 1 to 300 MPa, and more preferably at 3 to 200 MPa. The pressure treatment is preferably performed after the active material layer is formed into a layer.
[0374] In the pressurization treatment, the layer of the electrode composition (active material layer before the pressurization treatment) can be pressurized separately or in a state of being stacked with other layers. For example, the pressurization treatment can be performed after forming a laminate of an electrode composition layer for forming a positive electrode active material layer / a solid electrolyte layer / an electrode composition layer for forming a negative electrode active material layer.
[0375] The method of the pressure treatment is not particularly limited, and the pressure treatment may be performed by pressurizing or by sealing the container while pressurizing the container.
[0376] [Method for manufacturing all-solid-state secondary battery]
[0377] Regarding the manufacturing method of the secondary battery of the present invention, at least one of the positive active material layer and the negative active material layer is formed using the electrode composition of the present invention. In addition, it can be carried out with reference to the usual manufacturing method of the all-solid-state secondary battery. That is, the manufacturing method of the secondary battery of the present invention is a manufacturing method of an all-solid-state secondary battery in which a positive active material layer, a solid electrolyte layer and a negative active material layer are sequentially arranged, and it includes: using the electrode composition of the present invention to form at least one of the positive active material layer and the negative active material layer.
[0378] The method for forming the positive electrode active material layer and the negative electrode active material layer can be carried out by appropriately referring to the description of the above-mentioned [Method for Producing Electrode Sheet for All-Solid State Secondary Battery].
[0379] There is no particular limitation on the method for forming a laminate in which a positive electrode active material layer, a solid electrolyte layer and a negative electrode active material layer are sequentially arranged. For example, a positive electrode forming composition (positive electrode slurry) containing a positive electrode active material is applied to a metal foil as a positive electrode collector layer to form a positive electrode active material layer, and then a solid electrolyte layer forming dispersion (solid electrolyte slurry) containing a solid electrolyte is applied to the positive electrode active material layer to form a solid electrolyte layer, and further, a negative electrode forming composition (negative electrode slurry) containing a negative electrode active material is applied to the solid electrolyte layer to form a negative electrode active material layer, and a negative electrode collector layer (metal foil) is overlapped on the negative electrode active material layer. The whole can be pressurized as needed to obtain a product such as Figure 1 The all-solid-state secondary battery shown.
[0380] Furthermore, it is also possible to manufacture an all-solid-state secondary battery by reversing the method of forming each layer, forming a negative electrode active material layer, a solid electrolyte layer and a positive electrode active material layer on the negative electrode collector layer, and overlapping a positive electrode collector layer (metal foil) on the positive electrode active material layer, and pressurizing the entirety as needed.
[0381] As another method, the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer can be separately prepared, and they can be stacked in sequence between the positive electrode collector layer and the negative electrode collector layer as a positive electrode collector layer (metal foil), a positive electrode active material layer, a solid electrolyte layer, a negative electrode active material layer, a negative electrode collector layer (metal foil), and pressurized as needed to manufacture an all-solid-state lithium-ion secondary battery.
[0382] In this case, in the formation of each layer, supports such as nonwoven fabrics can be configured as required to make each layer a self-supporting film. In addition, usually, when stacking each layer and making a full solid-state lithium ion secondary battery, it is preferably used after removing the support in the self-supporting film.
[0383] The conditions for the press treatment are not particularly limited, and the press treatment can be performed under the same conditions and method as those for the press treatment in the method for producing the electrode sheet of the present invention.
[0384] The pressurization treatment may be performed on the layer itself formed using the electrode composition, or, when the layers are stacked as described above, may be performed on the layered body.
[0385] In addition, the manufacturing method of the secondary battery of the present invention is not limited to the manufacturing method described above as long as the secondary battery specified in the present invention can be obtained.
[0386] In the manufacture of the secondary battery of the present invention, even if a sulfide-based solid electrolyte is not used as the solid electrolyte, the formation of a layer that suppresses the interface resistance between solid particles or between layers can be achieved through the action of the above-mentioned oxide-based solid electrolyte (I) that can easily undergo plastic deformation under pressure.
[0387] The solid electrolyte (I) itself is soft and plastically deformable, and acts like a binder to help improve the adhesion between solid particles and between layers. Therefore, it is possible to form layers without using a binder such as an organic polymer.
[0388] The secondary battery of the present invention is preferably initialized after manufacture or before use. The initialization method is not particularly limited, and can be performed by, for example, performing initial charge and discharge under increased pressure and then releasing the pressure until the pressure condition is within the range when the secondary battery is used.
[0389] [Application of secondary batteries]
[0390] The secondary battery of the present invention can be applied to various purposes. The application mode is not particularly limited. For example, when it is carried on an electronic device, a notebook computer, a pen input computer, a mobile computer, an e-book reader, a mobile phone, a wireless telephone handset, a pager, a handheld terminal, a portable fax machine, a portable copier, a portable printer, a stereo headset, a video movie, a liquid crystal television, a handheld cleaner, a portable CD player, a mini disc player, an electric shaver, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio and a backup power supply can be cited. As other consumer products, automobiles, electric vehicles, motors, lighting equipment, toys, game consoles, load regulators, clocks, flashlights, cameras and medical equipment (pacemakers, hearing aids and shoulder massagers, etc.) can be cited. In addition, it can be used for various military purposes and space purposes. And, it can also be combined with solar cells.
[0391] The present invention will be described in further detail based on Examples, but the interpretation of the present invention is not limited to these Examples.
[0392] Example
[0393] [Reference Example 1: Production based on the above steps 0, 1A to 3A]
[0394] Using a ball mill (manufactured by Fritsch Japan Co., Ltd., planetary ball mill P-7), powdered Li2B4O7 crystals (LBO powder) (manufactured by RARE METALLIC Co., Ltd.) were ball-milled under the following conditions: pot: yttria-stabilized zirconia (YSZ) (45 mL), grinding balls: YSZ (average particle size: 5 mm, number: 50), rotation speed: 370 rpm (revolutions per minute), LBO powder amount: 1 g, atmosphere: air, ball mill processing time: 100 hours, thereby obtaining a micronized lithium-containing oxide (hereinafter also referred to as "micronized lithium-containing oxide").
[0395] 0.05 g of LiFSI (chemical formula: Li(FSO2)2N) was added as a lithium salt to 1 g of the obtained lithium oxide-containing fine material (5% by mass relative to the lithium oxide-containing fine material), and ball milling was performed for 100 hours. The obtained powder was added to water so that the powder concentration became 42% by mass, and ultrasonic dispersion was performed for 30 minutes. Then, the obtained dispersion was transferred to a glass petri dish and dried at 120°C for 2 hours in the atmosphere to obtain a thin film of a solid electrolyte. Then, the obtained film was peeled off to obtain a powdered solid electrolyte (II)-1.
[0396] <Production and evaluation of solid electrolyte molded body>
[0397] The powdered solid electrolyte (II)-1 obtained above was pressed at 27°C (room temperature) at an effective pressure of 220 MPa to obtain a solid electrolyte molded body (compressed powder body 1). The shape of the compressed powder body 1 was a cylindrical shape with a diameter of 10 mm and a thickness of 1 mm. The ionic conductivity of the compressed powder body 1 was measured and the ionic conductivity of the compressed powder body 1 was 1.5×10 -4 S / cm, and 4.0×10 at 60°C -4 S / cm.
[0398] The ionic conductivity of the above-mentioned solid electrolyte (II)-1 was calculated by the following method: electrodes consisting of two In foils were arranged in a manner of clamping the powder compact 1, and the AC impedance between the two In electrodes was measured in the measurement frequency range of 1 Hz to 1 MHz at a measurement temperature of 27°C or 60°C and an applied voltage of 50 mV, and the arc diameter of the obtained Cole-Cole diagram (Nyquist diagram) was analyzed.
[0399] As described above, using CuKα rays, X-ray diffraction measurement of solid electrolyte (II)-1 was performed. The measurement conditions were set to 0.01° / step and 3° / minute. The results showed that the above-mentioned X-ray diffraction characteristics were satisfied, which showed that solid electrolyte (II)-1 was in an amorphous state.
[0400] The solid electrolyte (II)-1 obtained in the above was used and the solid electrolyte (II)-1 was measured by SPring-8 L04B2 (accelerating voltage: 61.4 keV, wavelength: ) Total X-ray scattering measurements were performed. The samples were sealed in a 2 mm φ or 1 mm φ Kapton capillary and the experiment was performed. As described above, the obtained data were Fourier transformed to obtain the reduced two-body distribution function.
[0401] As a result of the analysis, it was confirmed that in the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement, when r is In the range of , the peak G(r) shows more than 1.0, and the peak is located at The first peak and the peak G(r) show more than 1.0, and the peak is located at The second peak of
[0402] On the other hand, in solid electrolyte (II)-1, the peaks attributed to the BO distance and BB distance observed in ordinary lithium tetraborate crystals are maintained. Ordinary lithium tetraborate crystals have a structure (diborate structure) in which BO4 tetrahedra and BO3 triangles exist in a 1:1 ratio, and it is inferred that in solid electrolyte (II)-1, this structure is maintained.
[0403] Solid electrolyte (II)-1 was prepared at 120 °C. 7 The full width at half maximum (FWHM 2) of the peak whose chemical shift appears in the range of -100 to +100 ppm in the spectrum obtained by Li-NMR measurement is relative to the solid electrolyte (II)-1 obtained above at 20°C. 7 The ratio of the full width at half maximum (FWHM 1) of the peak whose chemical shift appeared in the range of -100 to +100 ppm in the spectrum obtained in Li-NMR measurement {(FWHM 2 / FWHM 1)×100} was 33%.
[0404] Will be solid at 20℃ 7 When the waveform of the first peak appearing in the range of -100 to +100 ppm in the spectrum obtained during Li-NMR measurement is separated, a second peak having a chemical shift in the range of -3 to 3 ppm and a half-maximum width of less than 5 ppm is obtained, and the ratio of the area intensity of the second peak to the area intensity of the first peak is 4%.
[0405] The solid electrolyte (II)-1 obtained in the above-mentioned manner was used and infrared absorption spectrum was measured under the above-mentioned conditions. In the infrared absorption spectrum obtained, the -1 The maximum absorption intensity in the wave number region is relatively large compared to that in the region of 800 to 1600 cm -1 The ratio of the maximum absorption intensity in the wavenumber region is 0.72.
[0406] In the Raman spectrum of the solid electrolyte (II)-1 obtained above, the -1 The coefficient of determination obtained by least squares linear regression analysis in the wavenumber region is 0.9974.
[0407] As described above, the mass reduction rate of the solid electrolyte (II)-1 when heated from 25°C to 800°C was 29.8%.
[0408] Regarding the analysis of each element in the obtained solid electrolyte (II)-1, lithium and boron were quantitatively analyzed by ICP-OES, and fluorine and sulfur were quantitatively analyzed by combustion ion chromatography (combustion IC), and regarding N, the analysis mass of sulfur was estimated in consideration of each atomic weight in the Li salt, and regarding O, the analysis mass of the elements other than O was added and calculated as a difference from the total amount of powder. The results are shown in the following table.
[0409] [Reference Example 2: Production based on the above steps 1B to 3B and method 2]
[0410] 1 g of the lithium oxide-containing fine substance used in Reference Example 1 was added to water so that the concentration of the fine substance became 42 mass %, and ultrasonic dispersion was performed for 30 minutes. 0.05 g of LiFSI (chemical formula: Li(FSO2)2N) was added to the obtained dispersion as a lithium salt (5 mass % relative to the lithium oxide-containing fine substance), and ultrasonic dispersion was performed for 30 minutes.
[0411] The obtained dispersion was transferred to a glass petri dish and dried at 120° C. for 2 hours in the atmosphere to obtain a thin film of a solid electrolyte. Next, the obtained thin film was peeled off to obtain a powdered solid electrolyte (II)-2. Regarding the solid electrolyte (II)-2, various evaluations were performed in the same manner as in Reference Example 1 in the atmosphere. The results are summarized in the following table.
[0412] [Reference Example 3: Production based on the above steps 1B to 3B and method 3]
[0413] Using a ball mill (manufactured by Fritsch Japan Co., Ltd., planetary ball mill P-7), powdered Li2B4O7 (LBO powder) (manufactured by RARE METALLIC Co., Ltd.) was ball milled under the conditions of pot: YSZ (45 ml), grinding balls: YSZ (average particle size: 5 mm, weight: 70 g), rotation speed: 530 rpm (revolutions per minute), LBO powder amount: 4.2 g, atmosphere: air, and ball mill processing time: 100 hours to obtain a fine substance containing lithium oxide.
[0414] The obtained lithium oxide-containing fine substance was added to water so that the concentration of the fine substance became 42 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a dispersion liquid 1.
[0415] Next, 3.25 g of LiFSI (chemical formula: Li(FSO 2 ) 2 N) as a lithium salt was added to water so as to have a concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 2 .
[0416] The obtained dispersion 1 and solution 2 were mixed and stirred for 60 minutes with a magnetic stirrer. Then, the obtained dispersion was vacuum dried at 40°C and 10Pa for 15 hours to obtain a powdered solid electrolyte (II)-3. The obtained powder was allowed to stand for a certain period of time under the atmosphere, and various evaluations were performed under the atmosphere using the solid electrolyte (II)-3 in the same manner as in Reference Example 1. The results are summarized in the following table.
[0417] [Reference Example 4: Production based on the above steps 1B to 3B and method 3]
[0418] In the same manner as in the preparation of Dispersion Liquid 1 in Reference Example 3, Dispersion Liquid 3 was obtained.
[0419] Next, 2.32 g of LiFSI (chemical formula: Li(FSO 2 ) 2N) as a lithium salt was added to water at a concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 4 .
[0420] The obtained dispersion 3 and solution 4 were mixed and stirred for 60 minutes with a magnetic stirrer. Then, the obtained dispersion was vacuum dried at 40°C and 10Pa for 15 hours to obtain a powdered solid electrolyte (II)-4. The obtained powder was allowed to stand for a certain period of time under the atmosphere, and various evaluations were performed under the atmosphere using the solid electrolyte (II)-4 in the same manner as in Reference Example 1. The results are summarized in the following table.
[0421] [Reference Example 5: Production based on the above steps 1B to 3B and method 3]
[0422] In the same manner as in the preparation of Dispersion Liquid 1 in Reference Example 3, Dispersion Liquid 5 was obtained.
[0423] Next, 4.65 g of LiFSI (chemical formula: Li(FSO 2 ) 2 N) as a lithium salt was added to water at a concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 6 .
[0424] The obtained dispersion 5 and solution 6 were mixed and stirred for 60 minutes with a magnetic stirrer. Then, the obtained dispersion was vacuum dried at 40°C and 10Pa for 15 hours to obtain a powdered solid electrolyte (II)-5. The obtained powdered solid electrolyte (II)-5 was immediately used to perform various evaluations in the same manner as Reference Example 1 under the atmosphere. The results are summarized in the following table.
[0425] [Reference Example 6: Production based on the above steps 1B to 3B and method 3]
[0426] In the same manner as in the preparation of Dispersion Liquid 1 in Reference Example 3, Dispersion Liquid 7 was obtained.
[0427] Next, 7.13 g of LiTFSI (chemical formula: Li(F3CSO2)2N) as a lithium salt was added to water at a concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 8.
[0428] The obtained dispersion 7 and solution 8 were mixed and stirred for 60 minutes with a magnetic stirrer. Then, the obtained dispersion was vacuum dried at 40°C and 10Pa for 15 hours to obtain a powdered solid electrolyte (II)-6. The obtained powder was allowed to stand for a certain period of time under the atmosphere, and various evaluations were performed under the atmosphere using the solid electrolyte (II)-6 in the same manner as in Reference Example 1. The results are summarized in the following table.
[0429] In Reference Example 6, the carbon content shown in Table 1 below was estimated from the analyzed mass of sulfur in consideration of the atomic weights of the lithium salt.
[0430] [Comparative Reference Example 1]
[0431] The elemental analysis of the LBO powder (Li2B4O7 crystals in powder form without ball milling) used in Reference Example 1 showed that the composition of the LBO powder obtained was Li 1.96 B 4.00 O 6.80 The LBO powder was compacted at 27° C. (room temperature) at an effective pressure of 220 MPa to obtain a comparative reference powder compact C1. The ion conductivity of the obtained powder compact C1 could not be detected.
[0432] Furthermore, in the same manner as in Reference Example 1, total X-ray scattering measurement was performed using LBO powder to obtain the reduced two-body distribution function G(r). Fig.10 In FIG. 5 , the reduced two-body distribution function G(r) obtained from total X-ray scattering measurements is shown.
[0433] The analysis results show that in the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of LBO powder, there is a peak located at The first peak (corresponding to the vicinity of BO) and the peak are located at The second peak of the BB (corresponding to the BB), the peak G (r) of the first peak and the second peak is greater than 1.0 (reference Fig.10 ). In addition, there is a peak located at and The absolute value of the peak G(r) of each peak obviously exceeds 1.0 (ref. Fig.10 ).
[0434] Using CuKα rays, X-ray diffraction measurement was performed on the LBO powder of Comparative Reference Example 1. The measurement conditions were 0.01° / step and 3° / minute.
[0435] exist Fig.11 , the X-ray diffraction pattern of the LBO powder of Comparative Reference Example 1 is shown. Fig.11 As shown, in the LBO powder used in comparative reference example 1, multiple small peaks of width were observed. More specifically, the strongest peak corresponding to the (1,1,2) plane was observed at a position with a 2θ value of 21.78°. As other major diffraction peaks, a peak corresponding to the (2,0,2) plane was shown at a position of 25.54°, a peak corresponding to the (2,1,3) plane was shown at a position of 33.58°, and a peak corresponding to the (3,1,2) plane was shown at a position of 34.62°, and the intensities of these three peaks were roughly the same. These peaks originate from the crystal components.
[0436] [Comparative Reference Example 2]
[0437] The result of elemental analysis of the fine material containing lithium oxide prepared in Reference Example 1 (the material obtained by ball milling powdered Li2B4O7 crystals) showed that the composition of the fine material containing lithium oxide was Li 1.94 B 4.00 O 6.80 .
[0438] Next, the lithium oxide-containing fine material was pressed at 27°C (room temperature) at an effective pressure of 220 MPa to obtain a powder compact (powder compact R1) for comparative reference. The ion conductivity of the obtained powder compact R1 at 27°C was 7.5×10 -9 S / cm, and 7.5×10 at 60°C -8 S / cm.
[0439] In the following table, as described above, in the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement, there is a peak located at r The first peak and the peak top in the range of r are If the peak G(r) of the first peak and the peak G(r) of the second peak show a value greater than 1.0, the "Short-range G(r)" column is set to "A", and all other cases are set to "B".
[0440] In Reference Examples 1 to 5 and Reference Examples 9 to 13 shown in the following table, the value of the peak top G(r) of the first peak was 1.2 or more.
[0441] Furthermore, in the above-mentioned reduced two-body distribution function G(r), when r is greater than and When the absolute value of G(r) in the following range is less than 1.0, the "Long-range G(r)" column in the following table is set to "A", and when the absolute value of G(r) does not satisfy less than 1.0, it is set to "B".
[0442] In addition, the result of the X-ray diffraction measurement using the above-mentioned CuKα ray is set as "A" when the above-mentioned X-ray diffraction characteristics are satisfied, and "B" when the above-mentioned X-ray diffraction characteristics are not satisfied. In addition, in Reference Examples 1 to 6 shown in the following table and Reference Examples 7 to 13 described later, in the X-ray diffraction spectrum, the first peak, the second peak, the third peak, and the fourth peak are not present, or the intensity ratio of at least one of the first peak, the second peak, the third peak, and the fourth peak is 2.0 or less.
[0443] In the following table, in the "Elemental Analysis" column, the composition of the solid electrolyte (II) obtained in each reference example and the lithium-containing oxide in each comparative reference example is expressed as a relative value with the B content being "4.00" and expressed in terms of the molar amount of each element.
[0444] In the following table, blank means that the corresponding element is not contained.
[0445] In the following table, "half width ratio (%)", "coefficient of determination" and "mass reduction rate (%)" are the same as those described in the above description of Reference Example 1.
[0446] In the following table, the “area intensity ratio” is the ratio of the above solid state 7 In the Li-NMR measurement, the ratio of the area intensity of the second peak to the area intensity of the first peak was measured, and the evaluation results were described based on the following criteria.
[0447] <Standards for the ratio of area strength>
[0448] A: When the area strength ratio is 15% or more
[0449] B: When the ratio of area strength is 0.5% or more and less than 15%
[0450] C: When the ratio of area intensity is less than 0.5%
[0451] In the following table, the "Maximum Absorption Intensity Ratio" column indicates whether the above infrared absorption spectrum characteristics are met. -1 The maximum absorption intensity in the wave number region of 800 to 1600 cm -1 When the maximum absorption intensity in the wave number region is greater than 0.20, it is represented as "A", and when it is less than 0.20, it is represented as "B".
[0452] In the following table, "-" means that the measured value is not shown.
[0453] [Table 1]
[0454]
[0455] [Table 2]
[0456]
[0457] As shown in the above table, it can be seen that the solid electrolytes (II)-1, (II)-2, (II)-3, (II)-4, (II)-5 and (II)-6 of Reference Examples 1 to 6 have excellent ion conductivity. In addition, according to the results of elemental analysis, it was confirmed that the content of Li in the solid electrolytes of Reference Examples 3 to 6 was higher. In Reference Examples 3 to 6, the aqueous dispersion containing the lithium oxide subjected to mechanical milling and the aqueous solution containing the lithium salt (method 3 in the above step 2B) were mixed.
[0458] In addition, more lithium salt can be mixed, and as a result, it is presumed that the amount of Li entering the solid electrolyte has increased. In addition, it can be seen that in Reference Examples 3, 4, and 5 using LiFSI as the lithium salt, the ion conductivity is further improved.
[0459] This is presumably because the increased Li includes Li having high mobility.
[0460] <Effect of water in solid electrolyte>
[0461] The solid electrolyte (II)-3 powder compact (granules) (10 mm in diameter, 0.9 mm in thickness) obtained in Reference Example 3 was
[0462] The vacuum drying was performed under 60 MPa constraint and at 27°C, and the pressure change and ion conductivity with respect to the vacuum drying time were investigated. In addition, the method for preparing the powder compact and the ion conductivity evaluation were the same as described above except that the In electrode was changed to a Ti electrode. The results are shown in Table 3.
[0463] [Table 3]
[0464]
[0465] The solid electrolyte (II)-3 of Reference Example 3 has a wavelength of 3000-3500 cm in the infrared absorption spectrum. -1 In the wave number region of , a strong absorption intensity originating from the OH stretching peak was observed, so it is believed that a large amount of OH groups or water exists. In addition, regarding water, it is inferred that there are free water and bound water. In the above, the particles were first dried under conditions that are believed to volatilize from free water by vacuum drying, and then the particles were dried under strict drying conditions, so that the ion conductivity at each stage was evaluated.
[0466] As shown in the above table, the drying time was 5 minutes and the pressure was 200 Pa. It is considered that the free water was in a state of evaporation, but the ion conductivity showed 3.8×10 -3 S / cm, and the ionic conductivity showed 5.7×10 -4 S / cm. This result indicates that bound water in addition to free water exists and this contributes to ion conductivity.
[0467] [Reference Example 7: Production based on the above steps 1B to 3B and method 3]
[0468] In the same manner as in the preparation of the dispersion 1 in the above-mentioned Reference Example 3, a dispersion 9 having a concentration of 42% by mass of fine substances containing lithium oxide was obtained.
[0469] Next, 7.12 g of LiTFSI (chemical formula: Li(F 3 CSO 2 ) 2 N) as a lithium salt was added to water so as to have a concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 10 .
[0470] The obtained dispersion 9 and solution 10 were mixed and stirred for 60 minutes with a magnetic stirrer. Then, the obtained dispersion was vacuum dried at 40°C and 10Pa for 15 hours to obtain a powdered solid electrolyte (II)-7. The obtained powder was allowed to stand for a certain period of time in the atmosphere, and various evaluations were performed in the same manner as in Reference Example 1 using the solid electrolyte (II)-7 in the atmosphere. The results are summarized in the following table.
[0471] [Reference Example 8]
[0472] Solid electrolyte (II)-8 was obtained in the same manner as Reference Example 7 except that the contents of water and LiTFSI in the obtained solid electrolyte (II) were changed to the amounts described in the following table, and various evaluations were performed under air in the same manner as Reference Example 1. The results are summarized in the following table.
[0473] [Reference Examples 9 to 13]
[0474] Except that LiTFSI was changed to LiFSI and the contents of water and LiFSI in the obtained solid electrolyte (II) were changed to the amounts described in the following table, solid electrolytes (II)-9 to (II)-13 were obtained in the same manner as in Reference Example 7, and various evaluations were performed in the same manner as in Reference Example 1 under the atmosphere. The results are summarized in the following table. However, in Reference Example 13, the powder obtained by vacuum drying was immediately evaluated under the atmosphere.
[0475] In the following table, the columns "fine matter containing lithium oxide", "lithium salt" and "water" indicate relative molar ratios. For example, in Reference Example 7, the molar ratio of lithium salt to fine matter containing lithium oxide is 1, and the molar ratio of water to fine matter containing lithium oxide is 11. The above molar ratios were calculated by the following method.
[0476] Regarding the analysis of each element, lithium and boron were quantitatively analyzed by ICP-OES, and fluorine and sulfur were quantitatively analyzed by combustion ion chromatography (combustion IC). Regarding N, it was estimated based on the analytical mass of sulfur in consideration of each atomic weight in the Li salt, and regarding O, the analytical masses of elements other than O were added and calculated as a difference from the total amount of the solid electrolyte. In addition, in Reference Examples 7 and 8, regarding the carbon content, it was estimated based on the analytical mass of sulfur in consideration of each atomic weight in the lithium salt. The molar ratio of the fine matter containing lithium oxide in the solid electrolyte to the lithium salt was calculated based on the molar ratio of the element (e.g., B) present only in the fine matter containing lithium oxide to the element present only in the lithium salt. In addition, the molar ratio of the fine matter containing lithium oxide to water was calculated by subtracting the molar ratio of O contained in the fine matter containing lithium oxide and the lithium salt from the molar ratio of O in the solid electrolyte, and the molar amount of O derived from water was calculated using the obtained molar amount of O derived from water and the molar amount of the fine matter containing lithium oxide.
[0477] [Table 4]
[0478] Fine matter containing lithium oxide Lithium salts water Comparative Reference Example 2 1 0 0 Reference Example 7 1 1 11 Reference Example 8 1 1.2 11 Reference Example 9 1 0.01 4 Reference Example 10 1 0.03 4 Reference Example 11 1 0.5 11 Reference Example 12 1 0.7 11 Reference Example 13 1 1.0 6
[0479] Then, the content (mass %) of each component in the solid electrolyte (II) was calculated based on the molar amount and molecular weight described in Table 4. The results are shown in Table A below.
[0480] [Table A]
[0481] Fine matter containing lithium oxide Lithium salts water Comparative Reference Example 2 100 0 0 Reference Example 7 26 44 30 Reference Example 8 24 48 28 Reference Example 9 70 1 29 Reference Example 10 69 2 29 Reference Example 11 37 20 43 Reference Example 12 34 26 40 Reference Example 13 36 40 24
[0482] [Table 5]
[0483]
[0484] As shown in the above table, the solid electrolyte of each reference example has desired characteristics or properties and exhibits excellent ion conductivity.
[0485] <Preparation of electrode composition (slurry)>
[0486] (Example 1-1)
[0487] 1. Preparation of solid electrolyte
[0488] Using a ball mill (manufactured by Fritsch Japan Co., Ltd., planetary ball mill P-7), powdered Li2B4O7 crystals (LBO powder) (manufactured by RARE METALLIC Co., Ltd.) were ball milled under the following conditions: pot: yttria-stabilized zirconia (YSZ) (45 mL), crushing balls: YSZ (average particle size: 5 mm, number: 50), rotation speed: 370 rpm (revolutions per minute), LBO powder amount: 1 g, atmosphere: air, ball mill processing time: 100 hours, thereby obtaining a micronized lithium-containing oxide.
[0489] 0.05 g of LiFSI (chemical formula: Li(FSO2)2N) was added as a lithium salt to 1 g of the obtained lithium oxide-containing fine substance (5% by mass relative to the lithium oxide-containing fine substance), and ball milling was performed for 100 hours. The obtained powder was added to water so that the powder concentration became 42% by mass, and ultrasonic dispersion was performed for 30 minutes. Then, the obtained dispersion was transferred to a glass petri dish and dried at 120°C for 2 hours in the atmosphere to obtain a thin film of a solid electrolyte. Then, the obtained thin film was peeled off to obtain a powdery solid electrolyte SE1 (solid electrolyte for Example 1-1).
[0490] The particle size distribution of the solid electrolyte SE1 is about several μm to 30 μm, and the median diameter (D50) is 7.8 μm. The particle size distribution of the solid electrolyte is obtained by flow particle image analysis, and a histogram (particle size distribution) of the particle size of the solid electrolyte is prepared and calculated. The above particle size is equivalent to the equivalent circle diameter.
[0491] The results of analyzing the powder of the solid electrolyte SE1 confirmed that it had the above-mentioned X-ray diffraction characteristics and was in an amorphous state. In addition, the ion conductivity was measured by the above-mentioned method and the result was 1.5×10 - 4 S / cm. The element composition is the same as that of Reference Example 1.
[0492] 2. Preparation of active substances
[0493] Powdery LiCoO 2 crystals (LCO powder) (positive electrode active material) were classified into median diameters shown in the following table and used as active material AC.
[0494] The particle size distribution of the active material AC was about several μm to 20 μm, and the median diameter was 7.3 μm. The particle size distribution of the active material AC was measured using a laser diffraction / scattering particle size distribution measuring device (manufactured by HORIBA, Ltd., LA-920).
[0495] 3. Preparation of electrode composition (slurry)
[0496] 5 g of active material AC, 4.5 g of solid electrolyte SE1, 4.0 g of carbon nanotube (CNT) dispersion (solid content 12.5% by mass) (manufactured by KJ Specialty Paper Co., LTD.) and 0.5 g of water were added to a container, and stirred using an autorotation-revolution stirrer (manufactured by THINKY CORPORATION, trade name: Awatori Rentaro ARE310) at a rotation speed of 2000 rpm and a revolution speed of 800 rpm for 30 minutes to obtain a slurry SL-1 as an electrode composition with a solid content of 71.5% by mass.
[0497] (Examples 1-2 to 1-6, Comparative Examples 1-1 to 1-3)
[0498] The ball mill conditions were changed so that the median diameter of the solid electrolyte became the median diameter shown in the following table. In addition, an active material having a median diameter shown in the following table was used as the active material. Otherwise, a solid electrolyte and an active material were obtained in the same manner as in Example 1-1, and these were mixed in the same manner as in Example 1-1 to obtain each slurry.
[0499] (Examples 2-1 to 2-6, Comparative Examples 2-1 to 2-3)
[0500] Changing the active material from LCO powder to Li4Ti5O 12 (LTO powder) (negative electrode active material), the ball mill conditions were changed in a manner such that the median diameter of the solid electrolyte became the median diameter shown in the following table. In addition, an active material having a median diameter shown in the following table was used as the active material. Otherwise, a solid electrolyte and an active material were obtained in the same manner as in Example 1-1, and these were mixed in the same manner as in Example 1-1 to obtain each slurry.
[0501] (Examples 3-1 to 3-5, Comparative Examples 3-1 to 3-3)
[0502] The active material was changed from LCO powder to LiMn2O4 (LMO powder) (positive electrode active material), and the ball mill conditions were changed so that the median diameter of the solid electrolyte became the median diameter shown in the table below. In addition, an active material with a median diameter shown in the table below was used as the active material. Otherwise, a solid electrolyte and an active material were obtained in the same manner as in Example 1-1, and these were mixed in the same manner as in Example 1-1 to obtain each slurry.
[0503] (Examples 4-1 to 4-5, Comparative Examples 4-1 to 4-3)
[0504] Changed the active material from LCO powder to LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2 (NMC powder) (positive electrode active material), the ball mill conditions were changed in a manner so that the median diameter of the solid electrolyte became the median diameter shown in the following table. In addition, an active material with a median diameter shown in the following table was used as the active material. Otherwise, a solid electrolyte and an active material were obtained in the same manner as in Example 1-1, and these were mixed in the same manner as in Example 1-1 to obtain each slurry.
[0505] (Slurry concentration evaluation)
[0506] In this test, the suitability of the electrode composition (slurry) for high concentration was evaluated based on the maximum solid content concentration that could prepare the slurry without forming aggregates of 50 μm or more.
[0507] In this test, the active material and solid electrolyte having the median diameter shown in the following table used in each of the Examples and Comparative Examples were used to prepare a slurry according to the following procedure.
[0508] 5 g of active material, 4.5 g of solid electrolyte and water were added to a container and the amount of water was adjusted to achieve a predetermined slurry concentration. The mixture was stirred for 30 minutes at a rotation speed of 2000 rpm and a revolution speed of 800 rpm using an autorotation-revolution stirrer (manufactured by THINKY CORPORATION, trade name: Awatori RentaroARE310) to obtain a slurry.
[0509] The obtained slurry was poured into the deep side of the groove of a grinder (manufactured by Sansho Co., Ltd., trade name: Grind Gauge, maximum groove depth: 100μm, scale interval: 10μm), and the scraper was pulled toward the shallow side of the groove while being in vertical contact with the grinder to push the slurry away, and the state of the pushed slurry was visually observed to confirm whether streaks were observed above the scale of 50μm (on the side closer to the groove depth than the position of the scale of 50μm). The solid content concentration in the slurry was gradually increased, and the maximum concentration (the concentration before the concentration at which streaks were observed above the scale of 50μm) was used as the evaluation value, and the evaluation was performed using the following evaluation criteria.
[0510] --Evaluation Criteria--
[0511] A: 73% by mass or more
[0512] B: 70 mass% or more and less than 73 mass%
[0513] C: 65% by mass or more and less than 70% by mass
[0514] D: 60 mass% or more and less than 65 mass%
[0515] (Evaluation of electrode bending)
[0516] The flexibility of the electrode sheet was evaluated by a bending resistance test (in accordance with JIS K 5600-5-1: 1999) using a mandrel testing machine as follows.
[0517] The slurries (solid content 71.5% by mass) prepared in the above-mentioned examples and comparative examples were coated on a collector foil (20 μm thick A4 size Al foil) using a table-top coater so that the amount of the mixture (solid content) was 6 mg / cm 2 The mixture was dried by storing in a desiccator at a relative humidity of 5% or less for 12 hours, thereby producing an electrode stack (active material layer / Al current collector layer, before pressurization).
[0518] The obtained electrode laminate was pressed using a flat press at 5 MPa to obtain an electrode sheet.
[0519] A strip test piece with a width of 10 mm and a length of 100 mm was cut out from each electrode sheet. The surface of the active material layer side of the test piece was set on the side opposite to the mandrel (the collector was set to the mandrel side), and the width direction of the test piece was set to be parallel to the axis of the mandrel. After bending (1 time) 180° along the outer peripheral surface of the mandrel, it was visually observed whether cracks and / or peeling occurred in the active material layer. The test was first carried out using a mandrel with a diameter of 32 mm. Without any cracks or peeling, the diameter of the mandrel (in mm) was gradually reduced to 32, 25, 20, 16, 12, 10, 8, 6, 5, 4, 3, 2, and the diameter of the mandrel where cracks and / or peeling first occurred was recorded. The diameter (diameter of defect) at which the crack and / or peeling first occurred was evaluated for flexibility using the following evaluation criteria. In the present invention, the smaller the diameter indicating the defect, the more flexible the electrode sheet.
[0520] --Evaluation Criteria--
[0521] A: 3mm or less
[0522] B: 4mm or more and 6mm or less
[0523] C: 8mm or more and 10mm or less
[0524] D: 12mm or more
[0525] (Cycle Characteristics and Resistance Evaluation)
[0526] All-solid-state secondary batteries (Examples 20-01 to 20-06, Comparative Examples 20-01 and 20-02) were produced using the slurries obtained above, and their cycle characteristics and resistance were evaluated as follows. The details are shown below.
[0527] 1. Manufacturing of all-solid-state secondary batteries
[0528] 1) Preparation of positive electrode stack
[0529] As the positive electrode stack, each slurry described in Table 10 (slurries prepared in Examples 1-1 to 1-5, Comparative Examples 1-1 and 1-2 (solid content 71.5% by mass)) was applied on a collector foil (20 μm thick A4 size Al foil) using a tabletop coater so that the amount of the mixture (solid content) was 3 mg / cm 2 The mixture was dried by storing in a desiccator at a relative humidity of 5% or less for 12 hours, thereby preparing a positive electrode laminate (positive electrode active material layer / Al current collector layer, before pressurization).
[0530] 2) Fabrication of negative electrode stack
[0531] As the negative electrode stack, each slurry described in Table 10 (slurry prepared in Examples 2-1 to 2-6, Comparative Example 2-1, and Comparative Example 2-3 (solid content 71.5 mass %)) was applied to a collector foil (20 μm thick A4 size Al foil) using a tabletop coater so that the mixture was 2 mg / cm 2 The mixture was dried by storing in a desiccator at a relative humidity of 5% or less for 12 hours, thereby preparing a negative electrode laminate (negative electrode active material layer / Al current collector layer, before pressurization).
[0532] 3) Manufacturing of all-solid-state secondary batteries
[0533] The battery was manufactured using an all-solid-state battery evaluation cell (KP-SolidCell, manufactured by Hohsen Corp.).
[0534] Specifically, 80 mg of the solid electrolyte SE1 obtained above was put into a battery protection tube with a diameter of 10 mm, and pressurized at 60 MPa to form a solid electrolyte layer. The positive electrode stack obtained above was arranged on one side of the solid electrolyte layer in a manner of clamping the solid electrolyte layer, and the negative electrode stack obtained above was arranged on the other side of the solid electrolyte layer in a manner of facing the active material layer side to the solid electrolyte layer, and sealed at a pressure state of 60 MPa, thereby making an all-solid-state battery evaluation cell (all-solid-state secondary battery). In addition to the solid electrolyte layer, the all-solid-state secondary battery also has a positive electrode active material layer and a negative electrode active material layer formed by pressurizing each electrode composition layer.
[0535] 2. Cyclic characteristics test
[0536] The all-solid-state battery evaluation cell manufactured above was subjected to a charge and discharge test using an ABE1024-5V0.1A-4 charge and discharge tester (trade name, manufactured by Electricfield Company) to evaluate the cycle characteristics. The details are as follows.
[0537] The all-solid-state battery evaluation cell was initialized by charging and discharging at 1A under the following conditions.
[0538] (Condition 1A)
[0539]
[0540] The above was repeated 3 times.
[0541] The initialized all-solid-state battery evaluation cell was charged and discharged in the order of the following conditions 2A-1, 2A-2, and 2A-3.
[0542] (Condition 2A-1)
[0543]
[0544] (Condition 2A-2)
[0545]
[0546] The above-mentioned charge and discharge were defined as one cycle, and 29 cycles of charge and discharge were performed.
[0547] (Condition 2A-3)
[0548]
[0549] Discharge capacity retention rate A (%) = (discharge capacity under condition 2A-3) ÷ (discharge capacity under condition 2A-1) × 100, and the discharge capacity retention rate A was evaluated using the following evaluation criteria. A higher discharge capacity retention rate A indicates better cycle characteristics (longer cycle life).
[0550] --Evaluation Criteria--
[0551] A: More than 90%
[0552] B: 85% or more and less than 90%
[0553] C: 80% or more and less than 85%
[0554] D: 70% or more and less than 80%
[0555] E: 50% or more and less than 70%
[0556] F: less than 50%
[0557] 3. Battery resistance test
[0558] The all-solid-state battery evaluation cell manufactured above was subjected to a charge and discharge test using an ABE1024-5V0.1A-4 charge and discharge tester (trade name, manufactured by Electricfield Company) to evaluate the resistance of the battery. The details are as follows.
[0559] The all-solid-state battery evaluation cell was initialized by charging and discharging under the following condition 1B.
[0560] (Condition 1B)
[0561]
[0562] The above was repeated 3 times.
[0563] The initialized all-solid-state battery evaluation cell was charged and discharged under the following conditions 2B and 3B.
[0564] (Condition 2B)
[0565]
[0566] (Condition 3B)
[0567]
[0568] Discharge capacity retention rate B (%) = (discharge capacity under condition 3B) ÷ (discharge capacity under condition 2B) × 100, and the discharge capacity retention rate B was evaluated using the following evaluation criteria. The higher the discharge capacity retention rate B, the lower the resistance of the battery.
[0569] --Evaluation Criteria--
[0570] A: More than 96%
[0571] B: 94% or more and less than 96%
[0572] C: 92% or more and less than 94%
[0573] D: 87% or more and less than 92%
[0574] E: 80% or more and less than 87%
[0575] F: less than 80%
[0576] [Table 6]
[0577]
[0578] [Table 7]
[0579]
[0580] [Table 8]
[0581]
[0582] [Table 9]
[0583]
[0584] <Notes on the table>
[0585] In Tables 6 to 9, the unit of the median diameter of each solid electrolyte and each active material is "μm".
[0586] [Table 10]
[0587] Battery Positive electrode active material layer Negative electrode active material layer Resistance evaluation Cycle characteristics Example 20-01 Example 1-1 Embodiment 2-6 B B Example 20-02 Example 1-2 Example 2-2 B B Example 20-03 Examples 1-5 Example 2-3 A B Example 20-04 Examples 1-3 Embodiment 2-5 B C Example 20-05 Examples 1-4 Embodiment 2-4 A A Example 20-06 Examples 1-5 Example 2-1 B A Comparative Example 20-01 Comparative Example 1-1 Comparative Example 2-1 E E Comparative Example 20-02 Comparative Example 1-2 Comparative Example 2-3 F F
[0588] As shown in Tables 6 to 9 above, when the median diameter M of the active material in the electrode composition and the median diameter N of the solid electrolyte do not satisfy the 0.05≤M / N<1.2 specified in the present invention, an aggregate having a solid content of less than 70% by mass and 50 μm or more in the electrode composition is formed. In addition, the electrode sheet having an active material layer formed on the basis of setting the electrode composition to 71.5% by mass of solid content has poor flexibility.
[0589] In contrast, by controlling the ratio of the median diameter of the active material in the electrode composition to the solid electrolyte within the range specified in the present invention, the solid content in the electrode composition can be increased to 70% by mass or more without producing an agglomerate of 50 μm or more. It is believed that due to the effect of the water contained in the solid electrolyte, the affinity of the solid electrolyte surface and the dispersion medium is improved, and the particles of the solid electrolyte are particles that are difficult to precipitate. In addition, the electrode sheet having an active material layer formed on the basis of setting the electrode composition to a solid content concentration of 71.5% by mass shows excellent flexibility.
[0590] Furthermore, as shown in Table 10 above, a secondary battery having an active material layer formed using the above-mentioned high-concentration electrode composition whose median diameter ratio is not within the range specified in the present invention has a low discharge capacity ratio under 1C discharge and 2C discharge and a relatively high resistance, and also has poor cycle characteristics.
[0591] On the other hand, a secondary battery having an active material layer formed using the high-concentration electrode composition having a median diameter ratio within the range specified in the present invention has relatively low resistance and excellent cycle characteristics.
[0592] The present invention has been described together with its embodiments, but unless otherwise specified, it is understood that the present invention should not be limited to any details in the description and should be broadly interpreted within the scope of the spirit of the invention shown in the attached technical solutions.
[0593] This application claims priority based on Japanese Patent Application No. 2022-089968 filed in Japan on June 1, 2022, the contents of which are incorporated herein by reference as a part of what is described in this specification.
[0594] Explanation of symbols
[0595] 1-negative electrode collector, 2-negative electrode active material layer, 3-solid electrolyte layer, 4-positive electrode active material layer, 5-positive electrode collector, 6-working part, 10-all-solid-state lithium-ion secondary battery.
Claims
1. An electrode composition for an all-solid-state secondary battery, comprising an amorphous solid electrolyte and an active material, wherein: The solid electrolyte comprises: A metal oxide containing at least one of an alkali metal element and an alkaline earth metal element and an oxygen element, At least one metal salt selected from the group consisting of an alkali metal salt and an alkaline earth metal salt, and water, The ratio of the median diameter M of the active material to the median diameter N of the solid electrolyte is 0.05≤M / N<1.
2.
2. The electrode composition for an all-solid-state secondary battery according to claim 1, wherein The metal-containing oxide is a lithium-containing oxide containing Li, B and O, and the metal salt is a lithium salt.
3. The electrode composition for an all-solid-state secondary battery according to claim 1 or 2, wherein: The median diameter N of the solid electrolyte is 5 to 50 μm.
4. The electrode composition for an all-solid-state secondary battery according to any one of claims 1 to 3, wherein In the electrode composition for an all-solid-state secondary battery, the ratio of the content of the solid electrolyte to the content of the active material is, in terms of mass ratio, the solid electrolyte: the active material=20:80 to 80:
20.
5. The electrode composition for an all-solid-state secondary battery according to any one of claims 1 to 4, wherein In the solid electrolyte, the ratio of the content of the water to the content of the metal oxide is 1 to 12 in terms of molar ratio.
6. The electrode composition for an all-solid-state secondary battery according to any one of claims 1 to 5, wherein In the solid electrolyte, the ratio of the content of the metal salt to the content of the metal oxide is 0.001 to 1.5 in terms of molar ratio. 7 . An electrode sheet for an all-solid-state secondary battery, comprising an active material layer formed using the electrode composition for an all-solid-state secondary battery according to claim 1 .
8. An all-solid-state secondary battery, which is composed of a positive electrode active material layer, a solid electrolyte layer and a negative electrode active material layer in sequence, wherein: At least one of the positive electrode active material layer and the negative electrode active material layer is an active material layer formed using the electrode composition for an all-solid-state secondary battery according to any one of claims 1 to 6.
9. A method for manufacturing an electrode sheet for an all-solid-state secondary battery, comprising the following steps: An active material layer is formed using the electrode composition for an all-solid-state secondary battery according to any one of claims 1 to 6.
10. A method for manufacturing an all-solid-state secondary battery, wherein the all-solid-state secondary battery is sequentially configured with a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer, and the method for manufacturing the all-solid-state secondary battery comprises the following steps: At least one of the positive electrode active material layer and the negative electrode active material layer is formed using the electrode composition for an all-solid-state secondary battery according to any one of claims 1 to 6.
Citation Information
Patent Citations
Latex agglutination reaction measuring instrument
JP1987022066A
Catalyst carrier and production thereof
JP1990006856A
Four-wheel steering device
JP1991045473A
Distortion compensator
JP1993090844A
Assignment decision support system
JP1994004516A